Coating paste for forming microporous layer, its manufacturing method, and gas diffusion layer for fuel cell
Patent Information
- Application Number
- JP2022105803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-06-30
AI Technical Summary
【0031】 請求項1の発明に係るマイクロポーラス層形成用塗工ペーストによれば、カーボンブラックと、撥水性樹脂と、分散剤と、溶媒とを含有し、前記カーボンブラックは、DBP吸収量が300ml/100g以上、500ml/100g以下の範囲内であるカーボンブラックが目開き34~154μmの範囲内のメッシュを通過する2次凝集径のものであり、高DBP吸収量のカーボンブラックの二次凝集体が解砕されたものであるから、ペーストの粘度上昇が抑えられて、導電性多孔質基材の表面に対し良好な塗工性で塗布でき、塗布されたペーストが乾燥·焼成されることにより形成されるマイクロポーラス層においては、高DBP吸収量のカーボンブラックが高ストラクチャによる高空隙率を有することで、空隙率(気孔率)が高いものとなる。
Smart Images

Figure 0007640495000002 
Figure 0007640495000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating paste for forming a microporous layer, which is applied to the surface of a conductive porous substrate (gas diffusion layer electrode substrate) that constitutes a gas diffusion layer (GDL) for a fuel cell to form a microporous layer (MPL), and a manufacturing method thereof, as well as a gas diffusion layer for a fuel cell employing the same. In particular, the present invention relates to a coating paste for forming a microporous layer that can form a microporous layer with high porosity, a manufacturing method thereof, and a gas diffusion layer for a fuel cell employing the same. [Background technology]
[0002] In recent years, fuel cells, especially polymer electrolyte fuel cells (PEFCs), have been attracting much attention due to their potential for a wide range of applications, including automobiles, home power sources, and home appliances. A polymer electrolyte fuel cell uses an ion-conductive polymer membrane as an electrolyte, and a negative electrode and a positive electrode are bonded to this to form a single cell. Multiple single cells are then stacked with separators between them to generate high voltage.
[0003] In general, a single cell constituting a polymer electrolyte fuel cell has a cathode (+) electrode and an anode (-) electrode, which are composed of an electrode catalyst layer made of a conductive material such as carbon carrying a catalyst such as platinum and an ion exchange resin, and a porous gas diffusion layer (GDL) placed on the outside of the electrode catalyst layer, on both sides of a polymer electrolyte membrane (ion-conductive solid polymer electrolyte membrane) that selectively transmits specific ions, forming a membrane-electrode assembly (MEGA: Membrane-Electrode-Gas Diffusion Layer Assembly). In a polymer electrolyte fuel cell, a separator having gas flow paths for supplying fuel gas (anode gas) or oxidizing gas (cathode gas) and discharging generated gas and excess gas is disposed on the outside of the gas diffusion layer constituting the membrane / electrode assembly, and the membrane / electrode assembly is sandwiched between the separators to form a stack of multiple unit cells, thereby improving power generation.
[0004] Solid polymer fuel cells with this configuration are capable of generating energy with high efficiency and have a low environmental impact, and as such are increasingly being used as a power source (driving source) for automobiles. In order to further popularize their use as automobile fuel cells, there is a demand for increasing the output of the cells by improving the performance of the various components that make up the fuel cell.
[0005] In the configuration of such a polymer electrolyte fuel cell, as described above, in order to efficiently react the fuel gas (anode gas) and the oxidizing gas (cathode gas), a gas diffusion layer that guides the fuel gas or oxidizing gas supplied from the gas flow path of the separator is adjacent to a catalyst layer that supports a catalyst such as platinum and performs an electrochemical reaction. That is, the gas diffusion layer that constitutes the electrode of the single cell battery is formed to increase the diffusibility of the reactant gas, and plays a role (gas diffusibility, gas permeability) of diffusing the fuel gas or oxidizing gas supplied from the gas flow path of the separator to the adjacent catalyst layer. In addition, this gas diffusion layer between the separator and the catalyst layer is required to have a conductive function and a current collecting function to efficiently move electrons required for the electrochemical reaction. Furthermore, in order to improve and stabilize power generation performance, it is important to maintain the polymer electrolyte membrane in an optimal wet state in order to obtain high proton conductivity (electrical conductivity) in the electrodes, while quickly draining excess moisture in the catalyst layer to suppress the flooding phenomenon (the phenomenon in which the pores in the gas diffusion layer are blocked by water). The gas diffusion layer, which also serves as a moisture passageway, is required to have drainage properties (water repellency, moisture permeability) to appropriately take in the necessary moisture into the reaction system, while at the same time draining excess reaction water and condensation water generated by the electrochemical reaction of hydrogen and oxygen during power generation. The role of appropriately taking in and discharging moisture, i.e., moisture management through diffusivity, is also required.
[0006] In recent years, it has been proposed to form a coating thin film (sometimes called a microporous layer, carbon layer, or filling layer) called a microporous layer (MPL) mainly composed of a water-repellent resin such as PTFE and a conductive material such as carbon black on the conductive porous substrate (gas diffusion layer electrode substrate) that constitutes the gas diffusion layer, for example, made of carbon paper, carbon cloth, carbon felt, etc., to suppress the generation of a liquid film at the interface with the adjacent catalyst layer, promote water discharge and reverse diffusion of generated water, and improve the water management (water content control) of the solid polymer electrolyte fuel cell, thereby improving the power generation performance. In addition, by forming a microporous layer on the conductive porous substrate, the microporous layer also functions as a buffer material between the catalyst layer and the conductive porous substrate, and as a cosmetic effect that prevents the surface of the conductive porous substrate from being transferred to the electrolyte membrane. In addition, in a case where a microporous layer is formed by applying a paste for forming a microporous layer to a conductive porous substrate and drying and baking it, it is easy to finely control the characteristics of the gas diffusion layer by adjusting the paste components.
[0007] Here, examples of this type of known technology include Patent Document 1 and Patent Document 2. Patent Document 1 discloses a gas diffusion electrode substrate having a carbon sheet and a microporous layer, the carbon sheet being porous, the DBP oil absorption of the carbon powder contained in the microporous layer being 70 to 155 ml / 100 g, the microporous layer having a penetration index (L / W) calculated from the basis weight (W) of the microporous layer and the thickness (L) of the microporous layer being 1.10 to 8.00, and the thickness (L) of the microporous layer being 10 to 100 μm.
[0008] Patent Document 2 discloses a paste composition for forming a microporous layer, which contains carbon black, a water-repellent resin, a dispersant, and a solvent, and uses as the carbon black a first carbon black having a DBP absorption amount in the range of 210 ml / 100 g to 262 ml / 100 g and a second carbon black having a DBP absorption amount in the range of 32 ml / 100 g to 48 ml / 100 g, and further the iodine adsorption amount of the first carbon black is in the range of 85 mg / g to 97 mg / g, and the iodine adsorption amount of the second carbon black is in the range of 15 mg / g to 20 mg / g.
[0009] According to the technology of Patent Document 1, it is possible to suppress the penetration of the MPL coating liquid into the carbon sheet by increasing the DBP oil absorption of the carbon used to form the microporous layer (hereinafter sometimes abbreviated as "MPL"). Also, according to the technology of Patent Document 2, it is possible to suppress cracks in the MPL by combining carbon blacks with specific differences in the degree of structure development and controlling the chain structure and three-dimensional structure of the carbon particles.
[0010] Furthermore, Patent Documents 1 and 2 propose the use of carbon with a high DBP absorption, since carbon with little structure development and small DBP absorption is likely to penetrate into the conductive porous substrate made of a carbon sheet or the like when applied to the substrate, resulting in strike-through, and is also weak in strength and prone to cracking. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] International Publication No. 2016 / 076132 [Patent Document 2] JP 2019-040791 A (Patent No. 6932447 A) Summary of the Invention [Problem to be solved by the invention]
[0012] However, carbon with high DBP absorption has problems in that the structures (aggregates) tend to become entangled with each other, causing the structures to develop excessively (with secondary agglomerate diameters of several tens of μm or more), generating agglomerates (flocculated particles) and adsorbing and retaining large amounts of resin and solvent, resulting in poor dispersibility and an increase in the viscosity of the paint, which reduces coatability, causing surface defects in the gas diffusion electrode (reduced surface smoothness and narrower coating width) and reducing productivity. In addition, carbon products often contain foreign matter (impurities) such as sulfur, metals (potassium, lead, sodium, iron, etc.), calcium, chlorine, etc., and these foreign matter, particularly iron foreign matter, tend to reduce the durability and lifespan of the catalyst layer adjacent to the gas diffusion layer, thereby reducing battery performance and lifespan. When carbon with a high DBP absorption amount is blended into the coating paste for forming the MPL, the agglomerates can clog fine-mesh filtration filters used to remove foreign matter in carbon products, particularly iron foreign matter, reducing passability through the filtration filter, making it difficult to remove iron foreign matter and the like that reduces battery durability and lifespan.
[0013] Therefore, the use of carbon with a high DBP absorption amount causes aggregation and increases the viscosity of the coating paste, so there was a limit to the ability to improve the porosity (air porosity) and other performance aspects of the gas diffusion layer, such as the diffusivity, by using carbon with a highly developed structure.
[0014] Therefore, an object of the present invention is to provide a coating paste for forming a microporous layer, which can improve the performance of a gas diffusion layer by forming a microporous layer with a high porosity, a method for producing the same, and a gas diffusion layer for fuel cells. [Means for solving the problem]
[0015] The coating paste for forming a microporous layer of the invention of claim 1 contains carbon black, a water-repellent resin, a dispersant, and a solvent, wherein the carbon black has a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and has a secondary agglomeration diameter that passes through a mesh with an opening size of 34 to 154 μm. The coating paste is applied to the surface of a conductive porous substrate such as a carbon fiber sheet, and dried and fired to form a microporous layer of a gas diffusion layer for a fuel cell.
[0016] As the carbon black, for example, furnace black, thermal black, ketjen black, acetylene black, etc. can be used, but acetylene black is preferred since it can form a microporous layer having high gas diffusivity, strength, conductivity, etc. The carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g and a secondary aggregate size that passes through a mesh with an opening of 34 to 154μm means that the secondary aggregates (several tens of μm) of the carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g are disintegrated (disaggregated) by high shear dispersion to a secondary aggregate size (several μm) that can pass through a mesh with an opening of 34μm to 154μm, i.e., 100 mesh to 400 mesh. In other words, the carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g is disintegrated to have a secondary aggregate size that can pass through a mesh with an opening of 34 to 154μm (100 to 400 mesh).
[0017] Here, the "DBP absorption amount" is measured in accordance with JIS K6217-4. The DBP absorption amount (oil absorption amount) is determined by utilizing the fact that the porosity between carbon black aggregates is positively correlated with the structure, and by absorbing DBP (dibutyl phthalate) into the voids, the structure is indirectly quantified by the DBP absorption amount. The larger (higher) this value is, the more developed the carbon black structure is, and the higher the structure is, and the smaller (lower) the value is, the less developed the structure is, and the lower the structure is. The structure indicates the degree of development of chain-like aggregates (aggregates) consisting of several or several tens of carbon black particles, that is, the degree of development of the connections between carbon black particles. If the number of carbon particles constituting the aggregate is large or the aggregate has a complex shape, the DBP absorption amount is high. In this specification and claims, the mesh openings are those in accordance with the JIS G 3556 standard.
[0018] Claim 1 The coating paste for forming a microporous layer of the present invention has a viscosity at a shear rate of 50 [1 / s] of 0.05 Pa·s or more and 1.0 Pa·s or less, more preferably 0.1 Pa·s or more and 0.9 Pa·s or less, and even more preferably 0.1 Pa·s or more and 0.5 Pa·s or less.
[0019] The carbon black and the water-repellent resin in the coating paste for forming a microporous layer according to the invention of claim 2 have a solid weight ratio of 9 / 1≦carbon black / water-repellent resin≦5 / 5. do.
[0020] Claim 3 The manufacturing method of the coating paste for forming a microporous layer of the present invention involves mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin into a solvent in which a dispersant has been mixed and in which the dispersant has been dissolved and mixed, and stirring the mixture by a thin film swirling method.
[0021] Here, the thin film swirling method is a dispersion method in which the material to be treated (blended material) is rotated at high speed while being pressed against the inner wall surface of the device in a thin cylindrical shape by centrifugal force, and the shear stress generated by the centrifugal force and the speed difference between the inner wall surface of the device and the swirling flow is applied to the material to be dispersed (blended material), thereby creating a high-energy turbulent state throughout the tank, dispersing the aggregated particles in the thin cylindrical material to be treated (blended material). As a swirling thin film type high-speed agitator using such a high-speed swirling thin film flow, for example, the thin film swirling type high-speed mixer "Filmix" (registered trademark) series (manufactured by Primix Co., Ltd.) can be suitably used. The stirring conditions at this time are preferably a circumferential speed at the tip of the stirring blade of 25 m / s or more, and the circumferential speed is 25 m / s or more, and the upper limit is 60 m / s or less in terms of the performance limit of the machine. As the carbon black, for example, furnace black, thermal black, ketjen black, acetylene black, etc. can be used, but acetylene black is preferred because it is capable of forming a microporous layer having high gas diffusivity, strength, conductivity, etc.
[0022] Claim 4 The manufacturing method of the coating paste for forming a microporous layer of the present invention involves mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin into a solvent in which a dispersant has been mixed and in which the dispersant has been dissolved and mixed, and stirring the mixture at a peripheral speed of 25 m / s or more and 60 m / s or less.
[0023] Here, the mixing at a peripheral speed of 25 m / s or more refers to mixing at a peripheral speed of 25 m / s or more at the tip of the mixing blade using a high-speed mixer such as Homomixer, Homodisper, Neokaisa (registered trademark), Neomixa (registered trademark), thin film swirl type high-speed mixer, Homomixer, etc., the upper limit being 60 m / s or less in terms of the performance limit of the machine. Among them, the thin film swirl type high-speed mixer "Filmix" (registered trademark) series (manufactured by Primix Co., Ltd.) can be preferably used. As the carbon black, for example, furnace black, thermal black, ketjen black, acetylene black, etc. can be used, but acetylene black is preferred because it is capable of forming a microporous layer having high gas diffusivity, strength, conductivity, etc.
[0024] Claim 5 The method for producing a coating paste for forming a microporous layer of the present invention further comprises passing the mixture through a mesh having an opening of 34 to 154 μm (100 to 400 mesh), preferably a mesh having an opening of 45 to 154 μm (100 to 300 mesh), and more preferably a mesh having an opening of 45 to 150 μm (100 to 300 mesh), after the stirring.
[0025] Claim 6 The manufacturing method of the coating paste for forming a microporous layer of the present invention involves mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin into a solvent in which a dispersant has been mixed and in which the dispersant has been dissolved and mixed, pre-mixing with a disperser or a turbine-stator type mixer, and then mixing with a thin film rotation method or at a peripheral speed of 25 m / s or more and 60 m / s or less.
[0026] Here, the disperser described above stirs the material to be treated (mixed material) by generating shear through the high speed rotation of stirring blades such as a disk turbine or a dissolver (dispers). In addition, the above-mentioned turbine-stator type stirs the material to be treated (mixed materials) by applying shear force in the gap between the turbine and the stator.
[0027] Claim 7 The manufacturing method of the coating paste for forming a microporous layer of the present invention involves mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin into a solvent in which a dispersant has been mixed and in which the dispersant has been dissolved and mixed, pre-stirring at a peripheral speed of 1 m / s or more and 20 m / s or less, and then stirring by a thin film swirling method or at a peripheral speed of 25 m / s or more and 60 m / s or less.
[0028] Here, the stirring at a peripheral speed of 1 m / s or more and 20 m / s or less refers to stirring at a peripheral speed at the tip of the stirring blade by an agitator at 1 m / s or more and 20 m / s or less, preferably 10 m / s or more and 20 m / s or less, and for example, a Disper or turbine-stator type agitator can be used.
[0029] Claim 8 In the method for producing a coating paste for forming a microporous layer according to the present invention, the carbon black and the water-repellent resin have a solid content weight ratio of 9 / 1≦carbon black / water-repellent resin≦5 / 5.
[0030] Claim 9 The coating paste for forming a microporous layer in the method for producing a coating paste for forming a microporous layer of the present invention has a viscosity at a shear rate of 50 [1 / s] of 0.05 Pa·s or more and 1.0 Pa·s or less, more preferably 0.1 Pa·s or more and 0.9 Pa·s or less, and even more preferably 0.1 Pa·s or more and 0.5 Pa·s or less. Effect of the Invention
[0031] The coating paste for forming a microporous layer according to the invention of claim 1 contains carbon black, a water-repellent resin, a dispersant and a solvent, and the carbon black has a DBP absorption in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and has a secondary agglomerate diameter that passes through a mesh with an opening of 34 to 154 μm, and the secondary agglomerates of the carbon black with high DBP absorption have been broken down, so that an increase in the viscosity of the paste is suppressed and the paste can be applied with good coatability to the surface of the conductive porous substrate, and in the microporous layer formed by drying and firing the applied paste, the carbon black with high DBP absorption has a high porosity due to its high structure, resulting in a high porosity (air porosity).
[0032] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 to 154 μm, the paste has good coatability to ensure good surface smoothness in the microporous layer, and high porosity and coating strength that is less likely to cause cracks can be achieved at the same time. That is, a microporous layer can be formed that has high porosity, good surface smoothness, few cracks, and good adhesion to the catalyst layer. Therefore, the microporous layer is less likely to accumulate moisture and has high drainage, maintains high gas diffusivity, and has good durability. In addition, carbon black with a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and a secondary agglomeration diameter that passes through a mesh with an opening size of 34 to 154 μm is of a size that can pass through a fine mesh filter that enables the removal of foreign matter such as iron that affects the durability and lifespan of the catalyst layer in which the cell reaction takes place, and is therefore unlikely to reduce the durability and lifespan of the battery. Thus, the coating paste for forming a microporous layer according to the invention of claim 1 can form a microporous layer having a high porosity and capable of improving the gas diffusion properties and moisture management properties of the gas diffusion layer.
[0033] Claim 1 According to the coating paste for forming a microporous layer according to the present invention, -1 Since the viscosity at 200° C. is within the range of 0.05 Pa·s to 1.0 Pa·s, it is possible to suppress the strike-through of the paste (the phenomenon in which the paste penetrates to the back side of the conductive porous substrate opposite to the applied surface) when the paste is applied to the conductive porous substrate constituting the gas diffusion layer, and it is possible to form a cured coating film of a microporous layer with good smoothness at a desired coating width, resulting in good coatability. Therefore, a smooth microporous layer can be obtained without decreasing the porosity of the conductive porous substrate, and adhesion to the catalyst layer can be improved. , Ga It is possible to form a microporous layer that can better exhibit the performance of the gas diffusion layer.
[0034] Claim 2According to the coating paste for forming a microporous layer of the present invention, the weight ratio of the carbon black to the water-repellent resin is within the range of 9 / 1 to 5 / 5, so that the adhesiveness (binding property, binder effect) of the resin in the cured coating film of the formed microporous layer is good, cracks are unlikely to occur, and clogging of voids due to excess resin is suppressed. Therefore, in addition to the effect described in claim 1, a microporous layer can be formed that can achieve both coating film strength and gas and moisture permeability. do.
[0035] Claim 3 According to the method for producing a coating paste for forming a microporous layer of the present invention, carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g and a water-repellent resin are mixed in a solvent containing a dispersant and stirred by a thin film swirling method, and by dispersing the compounded materials with a high shear by the thin film swirling method, secondary agglomerates of carbon black with high DBP absorption can be broken down and an increase in viscosity of the paste can be suppressed. Therefore, the coating paste for forming a microporous layer in which secondary agglomerates of carbon black with high DBP absorption are broken down and an increase in viscosity is suppressed can be applied to the surface of a conductive porous substrate with good coatability, and in the microporous layer formed by drying and baking the applied paste, the carbon black with high DBP absorption has a high porosity due to its high structure, and thus has a high porosity (air porosity).
[0036] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 to 154 μm, the paste has good coatability, and the microporous layer has good surface smoothness, and high porosity and coating strength that is less likely to cause cracks can be achieved at the same time. That is, a microporous layer can be formed that has high porosity, good surface smoothness, few cracks, and good adhesion to the catalyst layer. Therefore, such a microporous layer is less likely to accumulate moisture and has high drainage properties, maintains high gas diffusivity, and has good durability. Therefore, the claim 3According to the method for producing a coating paste for forming a microporous layer of the present invention, a coating paste can be obtained that can form a microporous layer having a high porosity and that can improve the diffusion and moisture management performance of the gas diffusion layer.
[0037] Claim 4 According to the method for producing a coating paste for forming a microporous layer according to the present invention, carbon black having a DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g and a water-repellent resin are mixed in a solvent containing a dispersant and stirred at a peripheral speed of 25 m / s to 60 m / s, and the mixed materials are dispersed at a high shear speed by stirring at a peripheral speed of 25 m / s to 60 m / s, whereby secondary agglomerates of carbon black with high DBP absorption can be broken down and an increase in viscosity of the paste can be suppressed. Therefore, the coating paste for forming a microporous layer in which secondary agglomerates of carbon black with high DBP absorption are broken down and an increase in viscosity is suppressed can be applied to the surface of a conductive porous substrate with good coatability, and the applied paste is dried and fired to form a microporous layer, which has a high porosity (air porosity) due to the high structure of carbon black with high DBP absorption.
[0038] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 to 154 μm, the paste has good coatability, and the microporous layer has good surface smoothness, and high porosity and coating strength that is less likely to cause cracks can be achieved at the same time. That is, a microporous layer can be formed that has high porosity, good surface smoothness, few cracks, and good adhesion to the catalyst layer. Therefore, such a microporous layer is less likely to accumulate moisture and has high drainage properties, maintains high gas diffusivity, and has good durability. Therefore, the claim 4 According to the method for producing a coating paste for forming a microporous layer of the present invention, a coating paste can be obtained that can form a microporous layer having a high porosity and that can improve the diffusion and moisture management performance of the gas diffusion layer.
[0039] Claim 5 According to the method for producing a coating paste for forming a microporous layer according to the present invention, the mixture is passed through a mesh having an opening size of 34 to 154 μm after the stirring, so that the amount of foreign matter such as iron that affects the durability and life of the catalyst layer is reduced. 3 or claims 4 In addition to the effects described above, a coating paste can be obtained that can form a microporous layer that does not reduce the durability and lifespan of the battery.
[0040] Claim 6 According to the method for producing a coating paste for forming a microporous layer according to the present invention, a mixture of dispersant, solvent, carbon black, and water-repellent resin is pre-mixed using a Disper or turbine-stator type agitator before the mixing. In this way, by pre-mixing using a Disper or turbine-stator type agitator and then mixing using a thin film rotation method or at a peripheral speed of 25 m / s or more and 60 m / s or less, the carbon black and the solvent can become more compatible with each other through pre-mixing, and furthermore, by being able to mix and degas, it is possible to suppress variation in the distribution of secondary agglomeration diameter of the carbon black and also reduce air bubbles. Therefore, the present invention is not limited to the above-mentioned method. 3 or claims 4 In addition to the effects described above, a coating paste can be obtained that can form a more uniform microporous layer with reduced variation in void distribution.
[0041] Claim 7 According to the method for producing a coating paste for forming a microporous layer according to the present invention, before the stirring, a mixture of a dispersant, a solvent, carbon black, and a water-repellent resin is pre-stirred at a peripheral speed of 1 m / s or more and 20 m / s or less. In this way, when pre-stirring is performed at a low shear and then spreading is performed at a high shear, the pre-stirring can improve the compatibility of the carbon black with the solvent, and it is possible to suppress variation in the distribution of the secondary agglomeration diameter of the carbon black. Therefore, according to the present invention, 3 or claims 4In addition to the effects described above, a coating paste capable of forming a microporous layer in which the variation in pore distribution is suppressed can be obtained.
[0042] Claim 8 According to the method for producing a coating paste for forming a microporous layer according to the present invention, the weight ratio of the carbon black to the water-repellent resin is within the range of 9 / 1 to 5 / 5, so that the adhesiveness (binding property, binder effect) of the resin in the cured coating film of the formed microporous layer is good, cracks are unlikely to occur, and clogging of voids due to excess resin is suppressed. 3 or claims 4 In addition to the effects described above, a coating paste can be obtained that can form a microporous layer that has both coating strength and gas and moisture permeability.
[0043] Claim 9 According to the method for producing a coating paste for forming a microporous layer according to the present invention, -1 Since the viscosity at 200° C. is within the range of 0.05 Pa·s to 1.0 Pa·s, it is possible to suppress the strike-through of the paste (the phenomenon in which the paste penetrates to the back surface of the conductive porous substrate opposite to the surface to which the paste is applied) when the paste is applied to the conductive porous substrate constituting the gas diffusion layer, and it is possible to form a cured coating film of a microporous layer with good smoothness in a desired coating width, resulting in good coatability. Therefore, it is possible to obtain a smooth microporous layer and improve adhesion to the catalyst layer without decreasing the porosity of the conductive porous substrate, and therefore the present invention can be applied as claimed in claim 1. 3 or claims 4 In addition to the effects described above, a coating paste capable of forming a microporous layer that can better exhibit the performance of a gas diffusion layer can be obtained. [Brief description of the drawings]
[0044] [Figure 1] FIG. 1 is a schematic diagram showing the general configuration of a polymer electrolyte fuel cell using a gas diffusion layer formed by applying a coating paste for forming a microporous layer according to an embodiment of the present invention to a conductive porous substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the embodiments, the same symbols and the same reference characters denote the same or corresponding functional parts in the embodiments, so that repeated detailed explanations will be omitted here.
[0046] [Embodiment Mode] First, the structure of a polymer electrolyte fuel cell (single cell) incorporating a gas diffusion layer for a fuel cell on which a microporous layer is formed by applying a coating paste for forming a microporous layer according to this embodiment will be described with reference to the schematic diagram of Fig. 1. In the figure, the anode side is designated as A and the cathode side is designated as K.
[0047] 1, the gas diffusion layers 14 (cathode-side gas diffusion layer 14K, anode-side gas diffusion layer 14A) are made of catalyst-supported carbon, in which a precious metal catalyst such as platinum, gold, or palladium is supported by carbon, and ion exchange resin, and are joined to catalyst layers 13 (cathode-side catalyst layer 13K, anode-side catalyst layer 13A) with which an oxidizing gas or a fuel gas reacts, and are integrated to form the electrodes 12 (cathode electrode 12K, anode electrode 12A). The gas diffusion layers 14 are disposed together with the catalyst layers 13 on both sides of a polymer electrolyte membrane 11 (core of a single cell) that selectively allows specific ions to pass therethrough, forming a membrane / electrode assembly (MEGA) 10. This membrane / electrode assembly 10 is sandwiched between a cathode side separator 20K having an oxidizing gas flow path 21K for supplying an oxidizing gas that serves as an oxidant on the outside of the cathode side gas diffusion layer 14K, and an anode side separator 20A having a fuel gas flow path 21A for supplying a fuel gas on the outside of the anode side gas diffusion layer 14A, thereby forming a single cell of the fuel cell 1.
[0048] That is, the fuel cell 1 using the gas diffusion layer 14 to which the coating paste for forming a microporous layer according to this embodiment is applied has a cathode electrode 12K composed of a cathode side catalyst layer 13K and a cathode side gas diffusion layer 14K with which an oxidizing gas such as oxygen gas reacts arranged on one surface of a polymer electrolyte membrane 11, and an anode electrode 12A composed of an anode side catalyst layer 13A and an anode side gas diffusion layer 14A with which a fuel gas such as hydrogen gas reacts arranged on the other surface, and is composed of a membrane / electrode assembly 10 constituting a power generation section, a cathode side separator 20K arranged on the surface of the cathode electrode 12K of the membrane / electrode assembly 10, and an anode side separator 20A arranged on the surface of the anode electrode 12A of the membrane / electrode assembly 10.
[0049] Here, the gas diffusion layer 14 (cathode side gas diffusion layer 14K, anode side gas diffusion layer 14A) in this embodiment is formed by applying a coating paste for forming a microporous layer, which will be described later, to the surface of the conductive porous substrate 16 (cathode side conductive porous substrate 16K, anode side conductive porous substrate 16A) and drying and firing the coating paste, thereby forming a microporous layer (fine porous layer) 15 (cathode side microporous layer 15K, anode side microporous layer 15A) on one side of the conductive porous substrate 16 (cathode side conductive porous substrate 16K, anode side conductive porous substrate 16A). The gas diffusion layer 14 consisting of the microporous layer 15 and the conductive porous substrate 16 is assembled so that the microporous layer 15 side is adjacent to the catalyst layer 13 and the conductive porous substrate 16 side is adjacent to the separator 20 to form the fuel cell 1.
[0050] With such a cell configuration, when oxidizing gas is supplied from the outside to the oxidizing gas flow passage 21K of the cathode side separator 20K, a part of the oxidizing gas flowing along the oxidizing gas flow passage 21K penetrates into the inside from the surface of the conductive porous substrate 16K side of the cathode side gas diffusion layer 14K. The remaining unreacted oxidizing gas flows along the oxidizing gas flow passage 21K and is discharged to the outside of the fuel cell 1. Similarly, when fuel gas is supplied from the outside to the fuel gas flow passage 21A of the anode side separator 20A, a part of the fuel gas flowing along the fuel gas flow passage 21A penetrates into the inside from the surface of the conductive porous substrate 16A side of the anode side gas diffusion layer 14A. The remaining unreacted fuel gas flows directly along the fuel gas flow passage 21A and is discharged to the outside of the fuel cell 1. Then, the oxidizing gas and the fuel gas react with each other, and electricity is taken out between the cathode side separator 20K and the anode side separator 20A. The microporous layer 15 may be formed on both the front and back sides of the conductive porous substrate 16 .
[0051] Next, we will explain the coating paste for forming the microporous layer 15 that is applied to the fuel cell gas diffusion layer 14 (cathode side gas diffusion layer 14K, anode side gas diffusion layer 14A) that is incorporated into the fuel cell 1 having such a configuration.
[0052] The coating paste for forming a microporous layer in this embodiment (hereinafter sometimes abbreviated as "MPL coating paste") contains carbon black, which is a conductive material, a water-repellent resin, a solvent, a dispersant for dispersing the carbon black and the water-repellent resin, and the like.
[0053] The carbon black blended in the MPL coating paste of this embodiment has a DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g, preferably 300 ml / 100 g to 480 ml / 100 g, more preferably 300 ml / 100 g to 450 ml / 100 g. Such high DBP absorption carbon black has an average primary particle size in the range of about 25 nm to 45 nm, preferably 30 nm to 45 nm.
[0054] As the carbon black, furnace black, thermal black, acetylene black, Ketjen black, etc. can be used, but acetylene black is preferable. Acetylene black is highly structured, highly pure, has few impurities such as metals, has few surface functional groups, and is highly crystalline, so that a microporous layer 15 (hereinafter sometimes abbreviated as "MPL15") with high gas diffusivity, strength, and conductivity can be formed. Such carbon black has a structure in which primary particles are connected in a chain shape, i.e., the primary particles are fused to form an aggregate (primary agglomerate) structure, and further, the aggregates are bonded to each other by van der Waals forces to form agglomerates (secondary agglomerates), which then coagulate to form a powder or granular aggregate structure. Incidentally, carbon blacks such as acetylene black and ketjen black exhibit electrical conductivity due to the movement of π electrons in the condensed benzene ring. Furthermore, carbon black is less expensive than other types of carbon, so material costs are also low.
[0055] Examples of the water-repellent resin that can be used in the MPL coating paste include fluorine-based resins such as polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), perfluoroalkoxy fluorine resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), and polyvinylidene fluoride (PVdF), as well as silicone resins. These can be used alone or in appropriate combination of two or more.
[0056] Among these, fluorine-based polymer materials that are excellent in water repellency and corrosion resistance during electrode reactions are preferred, and in particular, PTFE, a fluororesin that provides high water repellency, is preferred. PTFE as a water-repellent resin may be a homopolymer of tetrafluoroethylene, or may be a modified PTFE that contains units derived from other fluorine-based monomers such as halogenated olefins such as chlorotrifluoroethylene and hexafluoropropylene, and perfluoro(alkyl vinyl ether).
[0057] In addition, the water-repellent resin preferably has an average molecular weight in the range of 50,000 to 1,000,000. If a resin with too low an average molecular weight is used, the binding ability as a binder for binding carbon black particles is small, and cracks are likely to occur in the MPL15 formed. On the other hand, if a resin with too large an average molecular weight is used, it is likely to become fibrous when mixed with other raw materials, resulting in poor dispersion, and the stability of the paste is reduced, or it becomes fibrous and solidifies due to the shear force during stirring, causing changes in concentration, clogging of pipes, pumps, foreign matter removal filters, etc., poor adhesion of the coating film, and surface defects. In addition, when the water-repellent resin is a fluoropolymer, it is difficult to measure the average molecular weight by melt viscosity because the fluoropolymer is difficult to dissolve in a solvent. For this reason, the specific gravity method is applied to determine the average molecular weight from the relationship between specific gravity and number average molecular weight.
[0058] Generally, water-repellent resins such as fluororesins do not disperse in water as they are, and therefore are dispersed in water using a suitable dispersant (surfactant), for example, in the form of an emulsion in which a water-repellent resin such as a fluororesin is emulsified, such as a PTFE emulsion, or in the form of a dispersion in which a water-repellent resin such as a fluororesin is dispersed, etc. That is, there are cases in which a dispersant is already contained in the emulsion of the water-repellent resin to be mixed as a composition raw material.
[0059] Incidentally, an emulsion is also called an emulsion, and its original meaning is a system in which liquid particles are in the form of colloidal particles or larger particles in a liquid and form a milk-like substance (dispersed system) (Iwanami Dictionary of Physics and Chemistry (5th Edition), edited by Nagakura Saburo et al., p. 152, published by Iwanami Shoten Co., Ltd. on February 20, 1998). However, in this specification, the term "emulsion" is used in the broader sense as "a system in which solid or liquid particles are dispersed in a liquid."
[0060] In addition, in the MPL coating paste of this embodiment, a dispersant is used to disperse and stabilize the compounding materials such as carbon black and water-repellent resin in the solvent. Examples of the dispersant include nonionic surfactants such as polyoxyethylene tridecyl ether, polyoxyethylene alkylphenyl ether (Triton X-100, etc.), polyoxyethylene lauryl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene alkylene alkyl ether, and polyethylene glycol alkyl ether; cationic surfactants such as alkyltrimethylammonium salt, dialkyldimethylammonium chloride, and alkylpyridinium chloride; and anionic surfactants such as polyoxyethylene fatty acid ester and acidic group-containing structurally modified polyacrylate; and thickeners such as polyethylene oxide, methylcellulose, hydroxyethylcellulose, polyethylene glycol (e.g., ethers of alkylphenol and polyethylene glycol, ethers of higher aliphatic alcohol and polyethylene glycol, etc.), and polyvinyl alcohol.
[0061] Among these, nonionic surfactants are preferred because they have a low metal ion content and are therefore less likely to cause a decrease in battery performance due to short circuits, etc. In particular, when carbon black and a PTFE emulsion as a water-repellent resin are dispersed in a solvent, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene alkyl phenyl ether (Triton X-100), etc. are preferably used to improve the wettability of the carbon black particles and PTFE particles and increase their dispersibility. The type of dispersant, such as a surfactant or thickener, is selected depending on the properties required of MPL15 and the ingredients used, and the dispersant may have both dispersing and thickening functions. Furthermore, if necessary, a thickener such as a polyvinyl alcohol-based thickener may be added to adjust the viscosity.
[0062] As the solvent for the MPL coating paste of this embodiment, an aqueous solvent such as ion-exchanged water is used. If an aqueous solvent such as ion-exchanged water is used, the water-repellent resin such as PTFE emulsion can be dispersed better than an organic solvent, and the water-repellent resin does not separate, resulting in good film-forming properties. In addition, the workability during coating and baking is good and there is no risk of fire. Furthermore, it is environmentally friendly and low cost.
[0063] In the MPL coating paste of this embodiment, the carbon black having a DBP absorption in the range of 300 ml / 100 g or more and 500 ml / 100 g or less, calculated on a solid content basis, is preferably blended in an amount of 55 to 90 mass %, more preferably 70 to 85 mass %, and even more preferably 75 to 80 mass %. The water-repellent resin is preferably blended in an amount of 10 to 45 mass %, more preferably 15 to 30 mass %, and even more preferably 20 to 25 mass %. The dispersant is preferably blended in an amount of 5 to 30 mass parts, more preferably 8 to 20 mass parts, and even more preferably 10 to 15 mass parts per 100 parts by mass of carbon.
[0064] The MPL coating paste of this embodiment is obtained through a dispersant mixing / dissolving process in which a solvent and a dispersant are mixed and stirred, a stirring process in which carbon black (usually in powder or granular form) having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin (usually in the form of a resin emulsion or resin dispersion) are mixed with the solvent in which the dispersant has been mixed and dissolved, and the mixture is stirred at a peripheral speed of 25 m / s or more using a thin film rotary stirrer or the like, and a filtration process in which the paste in which the blended materials have been dispersed by stirring is filtered through a mesh filter of a specified size to remove foreign matter.
[0065] That is, in this embodiment, first, a dispersant mixing / dissolving step is carried out in which the dispersant is mixed and dissolved in the solvent by mixing and stirring the dispersant and the solvent. The stirring means and stirring conditions at this time are not particularly limited as long as the dispersant can be uniformly mixed and dissolved in the solvent, and for example, if the dispersant is soluble in water, it can be made into a uniform solution by stirring with a stirrer (for example, stirring conditions of rotation speed: 100 to 1500 rpm (revolutions / min), stirring time: about 1 to 15 minutes).
[0066] Next, carbon black having a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and a water-repellent resin are mixed into the solvent in which the dispersant has been mixed and dissolved, A stirring step is carried out using a thin film rotary stirrer or the like at a peripheral speed of 25 m / s or more. In the above-mentioned stirring process at a peripheral speed of 25 m / s or more, stirring is performed at a peripheral speed of 25 m / s or more at the tip of the stirring blade using a high-speed stirrer such as Homomixer, Homodisper, Neokaisa (registered trademark), Neomixa (registered trademark), thin film swirling type high-speed mixer, or Homomixer. In particular, the agitation by the thin film swirling type agitator is called the thin film swirling method, and the entire inside of the agitator tank is put into a turbulent state of high energy. According to this agitation method, the agglomerated particles are pressed against the tank wall surface by the swirling flow that creates a turbulent state, and they perform a swirling motion along the wall surface. At this time, a swirling thin film is formed that is stretched thin by the rotation of the turbine and the liquid flow of the solvent, and the carbon black agglomerates are disintegrated by the shear stress of the centrifugal force pressed against the wall surface and the force that moves them by the swirling flow. Furthermore, in the agitation by this thin film swirling method, the re-agglomeration (flocculation) of the secondary agglomerates is prevented by stabilizing the droplet interface, and the disintegration state of the secondary agglomerates is stabilized. Carbon black with a high DBP absorption can be highly dispersed and the dispersion can be stabilized by a simple process without spending a lot of time. It is also possible to prevent the re-agglomeration (flocculation) of the secondary agglomerates that have been finely dispersed by such strong shearing, and to stabilize the disintegration state of the secondary agglomerates, using a dispersant.
[0067] The inventors have confirmed through their experimental research that if the peripheral speed of the stirring part is too slow or the stirring time is too short, the carbon black aggregates are not sufficiently disintegrated, making it difficult to pass the carbon black through a mesh filter with a specified mesh size under a specified pressure condition. Therefore, the stirring conditions in the thin film swirling stirrer, etc., are preferably set to a peripheral speed of 25 m / s or more, and the stirring time is preferably set to 20 seconds or more, more preferably 25 seconds or more, and even more preferably 30 seconds or more. The upper limit of the peripheral speed is a finite value at the performance limit (maximum peripheral speed) of the stirrer, which is about 60 m / s, but the inventors have confirmed through their experimental research that the desired viscosity characteristics can be obtained within a specified stirring time even at a peripheral speed of 50 m / s or more. In particular, in diffusion using such a thin film swirling method, it is possible to control the secondary aggregate diameter by changing the peripheral speed and stirring time conditions, and it is also possible to design the secondary aggregate diameter of carbon black according to the desired characteristics of MPL15.
[0068] Here, if the stirring time with a thin film swirling stirrer or the like is too long, the secondary agglomeration diameter of the carbon black becomes finer, and the viscosity of the paste decreases significantly. When the paste is applied to the conductive porous substrate 16 that constitutes the gas diffusion layer 14, the paste is likely to penetrate the conductive porous substrate 16 and pass through the thickness of the substrate. For this reason, it becomes necessary to increase the viscosity by adding a large amount of thickener. However, when a large amount of thickener is added, the load of decomposing and removing the thickener in the baking and drying process after the paste application increases. In other words, if the thickener is not sufficiently decomposed by the heat in the baking and drying process, it deteriorates the water repellency, so when a large amount of thickener is added, it becomes necessary to take a long drying and baking time, which increases the load of the baking and drying process. If the peripheral speed of the stirring part is preferably 25 m / s or more and the stirring time is preferably 20 to 200 seconds, more preferably 25 to 150 seconds, and even more preferably about 30 to 100 seconds, then it is possible to obtain a thickening agent at a shear rate of 50 S without the need to add a large amount of thickener. -1 It is possible to obtain the desired viscosity characteristics in the range of 0.05 to 1.0 Pa·S.
[0069] Then, by stirring for a predetermined time by a thin film rotation method or the like, the secondary agglomerates of carbon black can be disintegrated to a size that allows the paste to pass through a mesh with an opening of 154 μm or less, i.e., 100 mesh or more, which can remove metal foreign matter and the like contained in the carbon black product. However, since disintegration to a size that allows the paste to pass through a filter with too fine a mesh reduces productivity, it is sufficient that the secondary agglomerates of carbon black can be dispersed by the above stirring to a size that allows the paste to pass through a mesh with an opening of 34 μm or more and 154 μm or less, i.e., 100 mesh or more and 400 mesh or less, preferably, a mesh with an opening of 45 μm or more and 154 μm or less, i.e., 100 mesh or more and 300 mesh or less, and more preferably, a mesh with an opening of 45 μm or more and 150 μm or less, i.e., 100 mesh or more and 300 mesh or less.
[0070] Incidentally, when carrying out the present invention, pre-mixing (pre-dispersion) may be carried out, if necessary, by mixing with a disperse type or turbine stator type mixer before mixing with a thin film swirl type mixer or the like. By stirring with a Disper or turbine-stator type agitator before stirring with a thin film swirling agitator, the compounded materials are roughly dispersed, and the variation in the secondary agglomeration size distribution of the carbon black after stirring with a thin film swirling agitator can be suppressed (sharply adjusted particle size distribution) and the dispersion can be stabilized, resulting in high stability. In addition, it is possible to suppress the variation in the distribution of voids in MPL15, thereby obtaining stable performance and uniform diffusibility. This is thought to be because, by stirring with a Disper or turbine-stator type agitator at low shear before stirring with a thin film swirling agitator at high shear, the wettability of the carbon black and the affinity between the carbon black and the water solvent are improved, and the dispersibility by high shear stirring can be improved. And, if the carbon black has a highly developed structure, it can be assumed that it is easy to adsorb water and wet due to its large specific surface area. In addition, the wettability of carbon black can also be improved by using a dispersant.
[0071] Incidentally, the Disper type agitator generates shear force by rotating high-speed agitating blades called disk turbines or dissolvers at high speed. The turbine-stator type agitator is composed of a turbine blade (homogenizer) that rotates at high speed and a stator (fixed ring) that is formed to surround the periphery and does not rotate, and shear force is applied in the gap (clearance) between them. For example, homogenizers, comb-tooth turbine-stators, and in-line types (turbine-stator types installed inside a casing) can be used. A composite agitator that combines the Disper type and the turbine-stator side can also be used. All of these generate shear force by inputting energy locally. In particular, if a disperser type or turbine-stator type mixer is used, it is possible to create a paste that can form a uniform coating film with few bubbles by mixing and degassing the material.
[0072] The stirring conditions for a Disper-type or turbine-stator-type stirrer are a peripheral speed of 1 m / s or more and 20 m / s or less, preferably 10 m / s or more and 20 m / s or less. If the peripheral speed (rotation speed) of the stirrer is too low, the wettability of the carbon black particles cannot be sufficiently improved, and the variation in the distribution of the secondary agglomeration diameter of the carbon black cannot be effectively suppressed. On the other hand, if the rotation speed of the stirrer is higher than a certain level, even if the peripheral speed (rotation speed) or stirring time is too high, idling (vortexing) occurs, which does not affect the improvement of wettability and dispersibility, but only increases the load on the stirrer and energy consumption. If it is within the above range, the variation in the distribution of the secondary agglomeration diameter of the carbon black can be effectively suppressed with good productivity and low energy consumption. If a large amount of bubbles are generated by the stirring, a defoaming step may be performed before or after the stirring.
[0073] In this embodiment, after stirring with the thin film rotary stirrer, a filtration step is carried out in which the paste after stirring is filtered through a mesh filter with a predetermined mesh size to remove foreign matter such as iron. In this filtration step, the paste after stirring is passed through a filter with a mesh of 154 μm or less, i.e., a filter with a mesh of 100 mesh or more, using a ram press (pressure extrusion device) or the like. This removes foreign matter contained in the paste blending materials, particularly metal foreign matter such as iron contained in carbon black products that causes short circuits and adversely affects the durability of the catalyst layer 13 and the life of the battery 1. Since a filter with too fine mesh reduces productivity, it is preferable to use a mesh with a mesh of 34 μm or more and 154 μm or less, i.e., 100 mesh or more and 400 mesh or less, preferably a mesh with a mesh of 45 μm or more and 154 μm or less, i.e., 100 mesh or more and 300 mesh or less, and more preferably a mesh with a mesh of 45 μm or more and 150 μm or less, i.e., 100 mesh or more and 300 mesh or less.
[0074] At this time, the shear rate of the paste after mixing is 50S-1 If the viscosity exceeds 1.0 Pa·S, the pressure loss increases when passing the paste through a fine mesh to remove foreign matter, lowering productivity. -1 For those with a viscosity of more than 1.0 Pa·S at shear rate of 50 S, add a solvent and apply a shear rate of 50 S before passing through the specified filter. -1 It is preferable to adjust the viscosity so that the viscosity at a shear rate of 50 S is 1.0 Pa·S or less. -1 The viscosity is adjusted to 0.9 Pa·S or less, and more preferably 0.5 Pa·S or less.
[0075] Furthermore, in order to prevent the paste from penetrating through when the MPL coating paste is applied to the conductive porous substrate 16, the shear rate of the MPL coating paste applied to the conductive porous substrate 16 is set to 50 s -1 The viscosity at is preferably 0.05 Pa·S or more, and more preferably 0.1 Pa·S or more. In other words, if the viscosity of a paste that has been passed through a filter with a specified mesh size is too low, when it is applied to the conductive porous substrate 16 that constitutes the gas diffusion layer 14, the paste will penetrate into the conductive porous substrate 16, pass through the conductive porous substrate 16, and reach the back surface opposite the coated surface, causing a back-passage, and the paste components will clog the voids in the conductive porous substrate 16, reducing the permeability to gas and moisture.
[0076] Therefore, the shear rate of the paste after filtration through a filter with a specified mesh size is 50S -1 If the viscosity at a shear rate of 50 S is less than 0.05 Pa·S, the addition of a thickener will -1 The viscosity is adjusted so that the viscosity at a shear rate of 50 S is preferably in the range of 0.05 Pa·S or more and 1.0 Pa·S or less. -1If the viscosity at the shear rate is increased too much, the coatability of the MPL coating paste will decrease, and as described above, the load of the firing and drying process for decomposing the thickener will increase. -1 The viscosity at is preferably in the range of 0.05 Pa·S or more and 1.0 Pa·S or less, more preferably in the range of 0.1 Pa·S or more and 0.9 Pa·S or less, and even more preferably in the range of 0.1 Pa·S or more and 1.0 Pa·S or less.
[0077] The shear rate of the MPL coating paste applied to the conductive porous substrate 16 is 50S. -1 If the viscosity at 200° C. is within the range of 0.05 Pa·S or more and 1.0 Pa·S or less, then it is possible to prevent the paste from striking through when applied to the conductive porous substrate 16, thereby enabling the conductive porous substrate 16 to exhibit good performance, without increasing the load of the firing and drying processes, and since the coatability (surface smoothness, etc.) to the conductive porous substrate 16 is good, adhesion to the catalyst layer 13 is also good, and good moisture management and gas diffusivity are exhibited by the MPL 15. Note that the solid content will vary from this desired viscosity setting.
[0078] The MPL coating paste prepared in this manner is applied to the surface of the conductive porous substrate 16 that constitutes the gas diffusion layer 14 for the fuel cell 1, and then dried and fired to form a cured coating film that constitutes the MPL 15. As shown in Fig. 1, the gas diffusion layer 14 of the fuel cell electrode is constituted by the conductive porous substrate 16 as the gas diffusion layer electrode substrate and the MPL 15 as the cured coating film formed on one or both sides of the substrate.
[0079] Here, as the conductive porous substrate 16 to which the MPL coating paste of the present embodiment is applied, those generally used in the gas diffusion layer 14 of the conventional fuel cell 1 (particularly, solid polymer fuel cell 1) can be used, for example, those constituted by a carbon material (including nanocarbon material) such as metal or graphite in the form of a porous body such as fiber, particle, woven fabric, nonwoven fabric, mesh, lattice, punched body, foam, etc., and a porous substrate having gas permeability and conductivity is used. In particular, from the viewpoint of gas permeability, etc., carbon fiber (also called carbon fiber, carbon-based fiber, carbon-based fiber) is preferable, and polyacrylonitrile (PAN)-based carbon fiber, pitch-based carbon fiber, rayon-based carbon fiber, phenol-based carbon fiber, etc. are used as graphite fiber, etc. Carbon fiber sheets such as carbon paper, carbon cloth, and carbon felt (carbon nonwoven fabric) are preferably used as the form of the substrate. These are selected in consideration of the use environment, operating conditions, etc. of the fuel cell 1. Such a conductive porous substrate 16 is usually a porous body having a peak pore size within the range of 10 μm or more and 100 μm or less.
[0080] If necessary, the conductive porous substrate 16 such as carbon paper, carbon cloth, or carbon felt is subjected to a water-repellent treatment in order to improve the water repellency of the gas diffusion layer 14. The method of the water-repellent treatment is not particularly limited, and the water-repellent treatment can be performed, for example, by immersing the conductive porous substrate 16 in an emulsion or dispersion containing a water-repellent agent, applying the water-repellent agent to the conductive porous substrate 16 by die coating or spray coating, or processing by a dry process such as sputtering of a fluororesin. After the water-repellent treatment, drying and firing may be performed as necessary. The water-repellent agent used in this water-repellent treatment is the same as the above-mentioned water-repellent resin that can also be used in the MPL coating paste. The amount of the water-repellent agent at this time is not particularly limited, but from the viewpoint of achieving both water repellency and good gas diffusion paths and drainage paths, it is preferably within the range of 0.1% by mass to 20% by mass in the entire conductive porous substrate 16 (100% by mass).
[0081] The thickness of the conductive porous substrate 16 constituting the gas diffusion layer 14 for the fuel cell 1 is set in consideration of the operating conditions of the fuel cell 1 and the required performance, but if the conductive porous substrate 16 is too thin, the strength is insufficient, and the performance of the gas diffusion layer 14, such as stable gas diffusion, moisture management, and conductivity, cannot be obtained, or the handling property is poor, causing misalignment with the catalyst layer 13, resulting in a decrease in cell performance. Also, if the conductive porous substrate 16 is too thick, the resistance increases, causing a decrease in gas diffusion, and high cell performance cannot be obtained. For this reason, a substrate having a thickness of, for example, 2 μm or more and 500 μm or less, preferably 10 μm or more and 250 μm or less, and more preferably 70 μm or more and 150 μm or less is used.
[0082] Moreover, examples of the coating means for applying the MPL coating paste of this embodiment to the conductive porous substrate 16 include brush coating, roll coater method, bar coater method, die coater method, blade method, knife coater method, spin coater method, screen printing, rotary screen printing, curtain coating method, dip coater method, spray coater method, gravure coater method, applicator, spray atomization, etc. In particular, the die coater method is preferable because it allows the amount of coating to be quantified regardless of the surface roughness of the conductive porous substrate 16, but is not necessarily limited thereto.
[0083] The MPL coating paste of this embodiment is applied to the surface of the conductive porous substrate 16, dried and fired, and the solvent is dried and removed to form MPL 15 on the surface of the conductive porous substrate 16. The drying and firing temperature at this time may be any temperature that can decompose and remove dispersants such as surfactants and thickeners, and does not thermally decompose the water-repellent resin, and is, for example, heated for 5 to 20 minutes at a temperature in the range of 250 to 400°C. If the drying and baking temperature is too low, the dispersant and the like cannot be sufficiently thermally decomposed and volatilized to be removed even if the drying and baking time is extended, and the dispersant remains and the hydrophilic group of the dispersant captures moisture, so that the gas diffusion layer 14 formed does not exhibit sufficient water repellency. On the other hand, if the drying and baking temperature is too high, the coating film components such as the water-repellent resin are thermally decomposed, and the components of the MPL15 deteriorate, or the MPL15 is deformed greatly due to a large temperature change, resulting in a decrease in smoothness and cracks, making it difficult to form an MPL15 that meets the desired required performance. Furthermore, the load during the drying and baking process and the load on the natural environment increase, and the manufacturing cost also increases. By drying and baking within a specified temperature range, the dispersant and thickener such as surfactant contained in the MPL coating paste can be removed, preventing the inhibition of water repellency caused by the dispersant and thickener such as surfactant, and the carbon black can be bound by melting the water repellent, thereby forming an MPL15 with the desired strength.
[0084] For example, if the dispersant is polyoxyethylene tridecyl ether, polyoxyethylene alkylphenyl ether (Triton X-100), etc., the drying and baking temperature is set in the range of 250 to 350°C. Within this range, the dispersant, etc., is sufficiently decomposed and volatilized, so that the water repellency, which is an important characteristic of the gas diffusion layer 14 that greatly affects the power generation efficiency, can be secured, and the MPL 15 with the desired characteristics can be formed, and good bonding with the conductive porous substrate 16 can be secured. In addition, in such a drying and baking process involving heat treatment, the order of drying and baking is not particularly important, and drying and baking may be performed simultaneously. In addition, it is also possible to perform each heat treatment separately by changing the temperature and time conditions between the heat treatment mainly for decomposing and removing the dispersant and the heat treatment mainly for bonding by melting the water-repellent resin.
[0085] The coating thickness when the MPL coating paste of this embodiment is applied to the conductive porous substrate 16 is set in consideration of the operating conditions of the fuel cell 1 and the performance required of the MPL 15. For example, the thickness of the cured coating film after the MPL coating paste is applied to the conductive porous substrate 16 and dried and fired, i.e., the thickness of the MPL 15 as the dry film thickness, is set to be within the range of 1 to 300 μm, preferably within the range of 10 to 100 μm. If the thickness of the MPL 15 (dry film thickness of the cured coating film) is too thin, the effect of suppressing the formation of a liquid film at the interface with the catalyst layer 13 is small, and the effect of absorbing the irregularities of the conductive porous substrate 16 or preventing the fibers of the conductive porous substrate 16 from piercing the electrolyte membrane 11 cannot be obtained. On the other hand, if the coating thickness of the MPL coating paste is too thick, the surface smoothness is likely to decrease due to shrinkage caused by drying and baking, and the contact resistance with the catalyst layer 13 increases, leading to a decrease in adhesion, which leads to a decrease in moisture management and a decrease in conductivity. In addition, if the dry film thickness is too thick, the electrical resistance in the thickness direction increases, and further, the gas diffusion resistance also increases.
[0086] If the thickness of the cured coating film after applying the MPL coating paste to the conductive porous substrate 16 and drying and baking, that is, the dry film thickness of the MPL 15, is within the range of 1 to 300 μm, the MPL 15 with high surface smoothness can be obtained, and good gas and moisture permeability and conductivity performance can be ensured. It is preferably within the range of 10 to 100 μm. In addition, it is desirable that the thickness of the MPL 15 is 50% or less of the thickness of the conductive porous substrate 16. If the difference in thickness is within a moderate range, the shrinkage stress between the conductive porous substrate 16 and the MPL 15 due to drying and baking is small, and high bonding strength can be obtained. In addition, the smoothness of the entire gas diffusion layer 14 is increased, and the contact resistance with the catalyst layer 13 is reduced, so that good adhesion with the catalyst layer 13 exhibits good moisture management and conductivity.
[0087] By applying the MPL coating paste to the conductive porous substrate 16 in this manner and drying and baking the resulting product, the dispersant, thickener, and solvent (moisture) in the MPL coating paste are removed, and a cured coating film as MPL 15 in which carbon black is bound by the water-repellent resin is formed on the conductive porous substrate 16. At this time, the MPL coating paste is dried and baked together with the conductive porous substrate 16, so that part of the water-repellent resin in the MPL coating paste melts and bonds the carbon black together with the water-repellent resin, and also bonds the carbon black to the conductive material such as the carbon fiber of the conductive porous substrate 16, improving adhesion to the conductive porous substrate 16 and making the formed MPL 15 strong.
[0088] In this way, the MPL coating paste containing carbon black, water-repellent resin, dispersant and solvent is applied to the conductive porous substrate 16, followed by drying and baking to form a cured coating film MPL 15 on the conductive porous substrate 16. The cured coating film MPL 15 is composed of carbon black and water-repellent resin and is an extremely fine porous layer with pore diameters of approximately 0.1 to 0.5 μm. The cured coating film MPL 15 has electrical conductivity due to the carbon black, water repellency due to the water-repellent resin, and moisture and gas permeability due to the pores (voids).
[0089] Then, the MPL coating paste is applied to the surface of the conductive porous substrate 16, and the MPL 15 is formed on the conductive porous substrate 16 to form the gas diffusion layer 14 for the fuel cell. In the fuel cell 1 incorporating the gas diffusion layer 14, the presence of the MPL 15 makes it difficult for moisture to accumulate at the boundary with the adjacent catalyst layer 13, improving gas diffusion and moisture management, and stabilizing power generation performance. In addition, by adjusting the components of the MPL 15, it is possible to obtain fine control of performance according to the use environment and operating conditions of the battery, which is difficult to achieve with the conductive porous substrate 16 alone. Furthermore, the MPL 15 absorbs the undulations of the conductive porous substrate 16, resulting in a smooth surface. That is, the MPL 15 can prevent the occurrence of a short circuit caused by fraying or fluffing of the carbon fiber of the conductive porous substrate 16 piercing or contacting the catalyst layer 13 or the polymer electrolyte membrane 11.
[0090] In particular, according to the MPL coating paste of the present embodiment, secondary aggregates of carbon black with a high DBP absorption amount, which is within the range of 300 ml / 100 g to 500 ml / 100 g, are crushed, so that the viscosity increase of the paste is suppressed, and the paste can be applied to the surface of the conductive porous substrate 16 in a desired wide coating width, and coating streaks are unlikely to occur, resulting in good coating properties and good productivity. Furthermore, the MPL 15 formed from the MPL coating paste of the present embodiment has few unevenness or undulations such as coating streaks, good surface smoothness, good adhesion to the catalyst layer 13, little penetration into the catalyst layer 13, and little mechanical stress. In addition, since secondary aggregates of carbon black with a high DBP absorption amount are crushed by high-shear dispersion using a thin film spinning method or the like at a peripheral speed of 25 m / s or more, the aggregates are unlikely to re-aggregate, and storage stability is good.
[0091] And, because the carbon black with high DBP absorption has high porosity due to its high structure, the formed MPL 15 has high porosity (air porosity), and the pores can be distributed uniformly, and the high structure allows the formation of gas and moisture passages, thereby improving the diffusibility and drainage of gas and moisture. Therefore, flooding (the phenomenon in which generated water accumulates in the MPL) is less likely to occur, and the inhibition of gas diffusibility due to flooding is prevented. In addition, the inhibition of gas diffusibility and deterioration of the MPL 15 due to the freezing of moisture accumulated at the boundary with the catalyst layer 13 are prevented, and the battery output can be stabilized.
[0092] In addition, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the good coating property of the paste ensures good surface smoothness in the MPL 15, and high porosity and coating strength that is less likely to crack can be achieved at the same time. Therefore, by forming an MPL 15 that has high porosity but good surface smoothness, is less likely to crack, and has good adhesion to the catalyst layer 13, the MPL 15 is less likely to accumulate moisture, i.e., is less likely to cause flooding, and stable drainage and gas diffusion properties are obtained. In addition, the coating is less likely to chip and has good durability. The good adhesion to the catalyst layer 13 can reduce contact resistance at the contact surface, and also exhibit good conductivity without cracking, which can improve power generation efficiency. Furthermore, the material can withstand the clamping force from the separators during stacking, and the gaps are unlikely to be crushed even by the clamping force from the separators. Therefore, it is possible to form an MPL 15 with high porosity, improve the gas and moisture permeability of the MPL 15, and improve the gas diffusion and moisture management performance of the gas diffusion layer 14 in which the MPL 15 is formed.
[0093] Furthermore, when carbon black having a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary agglomeration diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the carbon black has a size that can pass through a fine mesh filter that enables the removal of foreign matter such as iron that affects the durability and lifespan of catalyst layer 13 in which the cell reaction occurs, and therefore has a good yield. Furthermore, the removal of foreign matter such as iron by filtration through a filter with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) makes it less likely to reduce the durability and lifespan of the battery.
[0094] Next, examples of the MPL coating paste according to this embodiment and examples of the fuel cell gas diffusion layer (gas diffusion electrode) 14 produced using the MPL coating paste according to this embodiment will be described together with comparative examples. The MPL coating paste of this example and the comparative example is a blend of carbon black, a water-repellent resin, a dispersant, and a solvent.
[0095] As the carbon black, acetylene black (for example, "Denka Black (registered trademark)" manufactured by Denki Kagaku Kogyo Co., Ltd.) was used, as the water-repellent resin, an emulsion of PTFE, a fluororesin (POLYFLON PTFE D-210C [solid content (resin content) 61%] manufactured by Daikin Industries, Ltd.) was used, as the dispersant, the surfactant Triton X-100 was used (10% blending in terms of carbon ratio), and as the solvent, ion-exchanged water was used. The PTFE emulsion also contains a non-ionic surfactant (dispersant) for stabilizing the PTFE fine particles as the water-repellent resin.
[0096] [Table 1]
[0097] In each of the Examples and Comparative Examples, the solvent and the dispersant were first mixed and stirred using a stirrer at a stirring speed of 300 rpm for about 10 minutes to dissolve the dispersant in the solvent (dispersant mixing and dissolving step). Next, the solvent in which the dispersant was dissolved was mixed with the specified carbon black and PTFE emulsion shown in Table 1, and stirred at 3000 rpm for about 30 minutes using a homomixer ("Homomixer MARK II 2.5 type" manufactured by Primix Corporation), which is a turbine-stator type high-speed stirrer, and then stirred under the specified conditions shown in Table 1 using Filmix R ("Filmix R56-L type" manufactured by Primix Corporation), which is a thin film swirling type high-speed stirrer (mixing step).
[0098] In Examples 1 to 4, Example 7, Comparative Example 1 and Comparative Example 2, the viscosity of the paste after stirring was measured by the thin film swirling method, and the viscosity was measured at a shear rate of 50 s-1 For pastes with a viscosity of 0.5 Pa·s or less at shear rate, the pastes were passed through a filter with a mesh size of 45 μm (300 mesh) at a pressure (pressing force) of 0.45 MPa using a ram press machine without any viscosity adjustment, and filtered to remove iron foreign matter (filtration process). Furthermore, the viscosity of the pastes after passing through the filter was measured, and the viscosity was measured at a shear rate of 50 s. -1 If the viscosity at this point was in the range of 0.1 Pa·s or more and 0.5 Pa·s or less, that was used as the MPL coating paste with the finished viscosity; if it was less than 0.1 Pa·s, a thickener was added to adjust the viscosity so that the finished viscosity was in the range of 0.1 Pa·s or more and 0.5 Pa·s or less, to obtain an MPL coating paste with a finished viscosity in the range of 0.1 Pa·s or more and 0.5 Pa·s or less.
[0099] On the other hand, the viscosity of the paste after stirring by the thin film swirling method was -1 For those with a viscosity exceeding 0.5 Pa·s at shear rate of 50 s, a solvent (ion-exchanged water) was added to adjust the viscosity so that it was within the range of 0.1 Pa·s to 0.5 Pa·s, and then a filtration process was carried out to remove iron foreign matter by passing the mixture through a filter with a mesh opening of 45 μm (300 mesh) under a pressure (pressing force) of 0.45 MPa using a ram press (filtration process).The viscosity of the paste after passing through the filter was then measured, and the viscosity was then measured again at a shear rate of 50 s as described above. -1 If the viscosity at this point was in the range of 0.1 Pa·s or more and 0.5 Pa·s or less, that was used as the MPL coating paste with the finished viscosity; if it was less than 0.1 Pa·s, a thickener was added to adjust the viscosity so that the finished viscosity was in the range of 0.1 Pa·s or more and 0.5 Pa·s or less, to obtain an MPL coating paste with a finished viscosity in the range of 0.1 Pa·s or more and 0.5 Pa·s or less.
[0100] In Example 5, after stirring by the thin film rotation method, the mixture was passed through a filter with a mesh size of 45 μm (300 mesh) under a pressure (pressing force) of 0.45 MPa using a ram press machine to remove iron foreign matter (filtration process). After that, the final viscosity was 50 S at a shear rate of 50 S. -1 Add solvent so that the viscosity at a shear rate of 50 S becomes 0.05 Pa s. -1 An MPL coating paste with a viscosity of 0.05 Pa·s was obtained. For Example 6, after stirring by the thin film swirling method, the final viscosity was 50 S at a shear rate of -1 A thickener was added so that the viscosity at a shear rate of 1.0 Pa·s was obtained, and then the mixture was passed through a 45 μm mesh (300 mesh) filter at a pressure of 0.45 MPa using a ram press to remove iron and other foreign matter (filtration process). -1 An MPL coating paste with a viscosity of 1.0 Pa·s was obtained.
[0101] In Examples 1 to 6, carbon black A having a DBP absorption capacity of 315 ml / 100 g ("Denka Black Li-250" manufactured by Denki Kagaku Kogyo Co., Ltd., average primary particle diameter: 37 nm, specific surface area: 58 m) was used. 2 / g, iodine adsorption capacity: 82 mg / g) (hereinafter abbreviated as "Carbon A") was used to prepare an MPL coating paste.
[0102] In Example 1, carbon A with a DBP absorption of 315 ml / 100 g was used, and the carbon / fluororesin (solid content) mixing ratio was 9 / 1. In the thin film swirling method, stirring was performed at a peripheral speed of 25 m / s for 30 seconds, and the final viscosity was 50 S at a shear rate. -1 The MPL coating paste has a viscosity of 0.5 Pa·s at 100° C. Note that the MPL coating paste according to Example 1 has a solid content ratio of carbon black, fluororesin, dispersant, etc. of 15%. In Example 2, carbon A with a DBP absorption of 315 ml / 100 g was used, the carbon / fluororesin (solid content) ratio was 9 / 1, and the thin film rotation method was used for stirring, with a peripheral speed of 50 m / s for 30 seconds, and the final viscosity was 50 S at a shear rate of 50 S. -1 The MPL coating paste has a viscosity of 0.1 Pa·s at 20° C. The solid content of the MPL coating paste in Example 2 is also 15%. In Example 3, carbon A with DBP absorption of 315 ml / 100 g was used, the carbon / fluororesin (solid content) blending ratio was 5 / 5, and the thin film swirling method was used for stirring at a peripheral speed of 25 m / s for 100 seconds, and the final viscosity was 50 S at a shear rate of 50 S. -1 The MPL coating paste has a viscosity of 0.1 Pa·s at 20° C. The solid content of the MPL coating paste in Example 3 is also 15%.
[0103] In Example 4, carbon A with DBP absorption of 315 ml / 100 g was used, the carbon / fluororesin (solid content) ratio was 5 / 5, and the thin film rotation method was used for stirring at a peripheral speed of 25 m / s for 30 seconds. The final viscosity was 50 S at a shear rate of 50 S. -1 The MPL coating paste in Example 4 has a viscosity of 0.5 Pa·s. The solid content of the MPL coating paste in Example 4 is 20%.
[0104] In Example 5, carbon A with a DBP absorption of 315 ml / 100 g was used, the carbon / fluororesin (solid content) ratio was 9 / 1, and the thin film rotation method was used for stirring, with a peripheral speed of 25 m / s for 30 seconds, and the final viscosity was 50 S at a shear rate. -1 The MPL coating paste in Example 5 had a viscosity of 0.05 Pa·s. The solid content of the MPL coating paste in Example 5 was 12%. In Example 6, carbon A with a DBP absorption of 315 ml / 100 g was used, the carbon / fluororesin (solid content) ratio was 9 / 1, and the thin film swirling method was used to stir the mixture at a peripheral speed of 25 m / s for 30 seconds, and the final viscosity was measured at a shear rate of 50 S. -1The MPL coating paste in Example 6 had a viscosity of 1.0 Pa·s. The solid content of the MPL coating paste in Example 6 was 15%.
[0105] Furthermore, in Example 7, carbon black B having a DBP absorption of 425 ml / 100 g ("Denka Black Li-100" manufactured by Denki Kagaku Kogyo Co., Ltd., average primary particle diameter: 35 nm, specific surface area: 68 m 2 Carbon B was used to prepare an MPL coating paste. In Example 7, carbon B with a DBP absorption of 425 ml / 100 g was used, the carbon / fluororesin (solid content) ratio was 9 / 1, and the thin film rotation method was used for stirring at a peripheral speed of 25 m / s for 30 seconds. The final viscosity was 50 S at a shear rate of 100 s. -1 The MPL coating paste in Example 7 has a viscosity of 0.5 Pa·s. The solid content of the MPL coating paste in Example 7 is 8%.
[0106] On the other hand, in Comparative Example 1, carbon black C ("Denka Black Li-400" manufactured by Denki Kagaku Kogyo Co., Ltd., average primary particle diameter: 48 nm, specific surface area: 39 m) with a DBP absorption of 220 ml / 100 g was used. 2 Carbon C was used to prepare an MPL coating paste. In Comparative Example 1, carbon C with DBP absorption of 220 ml / 100 g was used, the carbon / fluororesin (solid content) blending ratio was 9 / 1, and the thin film swirling method was used to stir the mixture at a peripheral speed of 10 m / s for 30 seconds, and the final viscosity was 50 S at a shear rate. -1 The MPL coating paste has a viscosity of 0.5 Pa·s at 20° C. The solid content of the MPL coating paste according to Comparative Example 1 is 13%.
[0107] In Comparative Example 2, carbon D (Denka Black Li-435 manufactured by Denki Kagaku Kogyo Co., Ltd., average primary particle diameter: 23 nm, specific surface area: 133 m) with a DBP absorption capacity of 510 ml / 100 g was used. 2 / g, iodine adsorption capacity: 180 mg / g) (hereinafter abbreviated as "Carbon D") was used to prepare an MPL coating paste. In this Comparative Example 2, carbon D with DBP absorption of 510 ml / 100 g was used, the carbon / fluororesin (solid content) blending ratio was 5 / 5, and the thin film swirling method was used to stir the mixture at a peripheral speed of 10 m / s for 30 seconds, and the final viscosity was 50 S at a shear rate of 50 S. -1 The MPL coating paste has a viscosity of 0.5 Pa·s at 20° C. The solid content of the MPL coating paste according to Comparative Example 2 is 13%.
[0108] The DBP absorption amount (ml / 100 g) of the carbon black was determined in accordance with JIS K 6217-4 by detecting the torque generated by the change in viscosity characteristics when DBP (dibutyl phthalate) is added to carbon black using an S-500 absorption amount measuring device (manufactured by Asahi Research Institute), and converting the amount of DBP added at 70% of the maximum torque into a value per 100 g of sample. The above viscosity was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd.).
[0109] Here, the MPL coating pastes of each Example and Comparative Example were evaluated for passability through a predetermined filter for removing iron foreign matter and the like. As described above, the MPL coating pastes of each Example and Comparative Example were extruded and passed through a 300-mesh filter with an opening of 45 μm using a ram press machine at a pressing force of 0.45 MPa. The MPL coating pastes that could pass through the 300-mesh filter with an opening of 45 μm without any deformation at that time at an extrusion pressure of 0.45 MPa suppressed clogging of the filter due to carbon black aggregates (aggregated particles), easily passed through a fine-mesh filter for removing iron foreign matter and the like contained in carbon black products, and had good productivity. In addition, the viscosity characteristics (flow characteristics) when applied to the conductive porous substrate 16 were good, and the coating properties with good smoothness were obtained, and were evaluated as ◎. Filters that were slightly deformed during extrusion of the MPL coating paste were evaluated as ◯, and filters that were broken were evaluated as × due to the decrease in productivity and the decrease in the removal rate of iron foreign matter and the like. The evaluation results at this time are as shown in the lower part of Table 1.
[0110] Furthermore, the MPL coating paste according to each of the examples and comparative examples was applied using a thin film application tool (die head) at a moving speed of 1.0 m / min and a basis weight of 3.5 mg / cm. 2 Under the above conditions, the conductive porous substrate 16 was coated on one side of a nonwoven carbon fiber sheet that had been impregnated with a fluororesin solution and treated for water repellency, and then dried and fired at 300° C. for 10 minutes. As a result, a cured coating film that became MPL 15 was formed from the MPL coating paste coated on the surface of the water-repellent treated nonwoven carbon fiber sheet as the conductive porous substrate 16, and a gas diffusion layer 14 was produced that was composed of the conductive porous substrate 16 made of the nonwoven carbon fiber sheet and the MPL 15 made of the cured coating film formed from the MPL coating paste.
[0111] At this time, for the MPL coating pastes according to each Example and Comparative Example, the viscosity characteristics of the paste when applied to a water-repellent treated nonwoven carbon fiber sheet as the conductive porous substrate 16 were observed from the appearance of strike-through (the phenomenon in which the paste penetrates to the back side of the conductive porous substrate 16 opposite to the coating surface). When the MPL coating pastes of each Example and Comparative Example were applied to a water-repellent treated nonwoven carbon fiber sheet, even if the MPL coating paste penetrated into the water-repellent treated nonwoven carbon fiber sheet, the circumscribed circle of the penetrated part of the MPL coating paste was 6 mm on the surface opposite to the coating surface of the nonwoven carbon fiber sheet. 2 / piece or less, the components of the MPL coating paste fill the voids (pores) of the conductive porous substrate 16, thereby suppressing the decrease in moisture and gas permeability, and the paste components have a moderately high viscosity characteristic (flow characteristic) that can suppress the penetration of the paste components to the back side, and is evaluated as ◎. 2 / pieces exceed 3 pieces / m 2 The following items were rated as ◯.
[0112] Furthermore, the MPL coating paste of each Example and Comparative Example was applied to a water-repellent treated nonwoven carbon fiber sheet, and dried and baked to form a cured coating film as MPL15 on the nonwoven carbon fiber sheet, and the presence or absence of surface cracks was confirmed using an optical microscope. Specifically, optical microscope photographs of 10 mm x 10 mm size were taken at any 10 points of the cured coating film as MPL15 formed on the nonwoven carbon fiber sheet, and if there were two or less cracks (cracks in the coating film) with a major axis length of 0.5 mm or more at 9 or more of the arbitrary 10 points, the coating film was judged to have excellent coating strength and rated as ⊚, and if there were three or more cracks with a major axis length of 0.5 mm or more at 8 or more points, the coating film was judged to be impractical and rated as x.
[0113] In addition, the MPL coating paste of each Example and Comparative Example was applied to a water-repellent treated nonwoven carbon fiber sheet, and dried and baked to form a cured coating on the nonwoven carbon fiber sheet to produce a gas diffusion layer 14 composed of a conductive porous substrate 16 made of a nonwoven carbon fiber sheet and an MPL 15 made of a cured coating formed from the MPL coating paste. The gas diffusion resistance of the gas diffusion layer 14 was measured to evaluate the gas diffusivity. Specifically, a circular sample with a diameter of 4.7 cm was cut out from the produced gas diffusion layer 14, and air was blown from the MPL 15 side of the gas diffusion layer sample to the opposite side at a flow rate of 58 cc / min / cm. 2 The gas diffusion resistance was examined by measuring the differential pressure between the MPL15 side and the opposite side (the nonwoven carbon fiber sheet side) with a differential pressure gauge when gas was allowed to permeate at a flow rate of 1000 rpm. The smaller the differential pressure, the smaller the gas diffusion resistance and the higher the gas diffusivity (gas permeability). Those with a gas diffusion resistance of 25 mmAq or less were judged to have excellent gas diffusivity and were rated as ⊚, and those with a resistance of more than 25 mmAq and less than 50 mmAq were rated as x. The evaluation results are shown in the lower part of Table 1.
[0114] As shown in Table 1, the MPL coating pastes of Examples 1 to 7 were prepared by using carbon black with a DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g, specifically, carbon A with a DBP absorption of 315 ml / 100 g and carbon B with a DBP absorption of 425 ml / 100 g, mixing the compounded materials with a turbine-stator type mixing system, and then mixing with a high share of a peripheral speed of 25 m / s or more by a thin film swirling method. All of the MPL coating pastes could easily pass through a filter with a mesh opening of 45 μm (300 mesh) at a pressing force of 0.45 MPa without significantly deforming the filter, i.e., without causing clogging.
[0115] Furthermore, all of the MPL coating pastes of Examples 1 to 7 had little bleed-through when applied to a nonwoven carbon fiber sheet serving as the conductive porous substrate 16, and had suitable viscosity characteristics and excellent coatability. Furthermore, the MPL15 cured coating film formed by applying the MPL coating paste of Examples 1 to 7 to a water-repellent treated nonwoven carbon fiber sheet and drying and baking it had few cracks on the surface and excellent coating strength.
[0116] According to the MPL coating pastes of Examples 1 to 7, which used carbon black with a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g, a gas diffusion layer 14 with excellent gas diffusivity could be obtained. That is, the MPL 15 formed of a cured coating film was prepared by applying the MPL coating pastes of Examples 1 to 7, which used carbon black with a DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g, to a water-repellent treated nonwoven carbon fiber sheet, and then drying and baking the MPL coating pastes. The gas diffusion layer 14 was composed of a conductive porous substrate 16 made of a nonwoven carbon fiber sheet, and had a smaller differential pressure, improved gas permeability, and excellent gas diffusivity, compared to Comparative Example 1, which used carbon black with a DBP absorption of 220 ml / 100 g. This is because carbon black with a DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a well-developed structure, so even when dispersed at a high shear, the primary aggregates maintain a high degree of porosity, thereby increasing the porosity of MPL15 formed as the cured coating film of the MPL coating paste.
[0117] In contrast, in the MPL coating paste of Comparative Example 1, which uses carbon black with a DBP absorption of less than 300 ml / 100 g, specifically carbon C with a DBP absorption of 220 ml / 100 g, the shear rate was 50 s. -1 Even when the viscosity at the final stage was 0.5 Pa·S, the resulting gas diffusion layer 14 had poor gas diffusivity.
[0118] Furthermore, in the cured coating film of MPL15 formed from the MPL coating paste of Comparative Example 2, which used carbon black with a DBP absorption exceeding 500 ml / 100 g, specifically, carbon D with a DBP absorption of 510 ml / 100 g, many cracks were observed and the coating film strength was poor. This is thought to be because carbon black with a DBP absorption of more than 500 ml / 100 g has a highly developed structure, so even when it is dispersed at a high shear and the secondary agglomerates are broken down, the primary agglomerates maintain a high porosity. With carbon black with a DBP absorption of more than 500 ml / 100 g, the porosity of MPL15 becomes too high, reducing the coating strength and causing many cracks.
[0119] That is, if the DBP absorption amount is too high, the porosity becomes too high, and the cured coating film of MPL15 becomes brittle, but if the cured coating film of MPL15 is brittle, the adhesion to the catalyst layer 13 also decreases, and flooding in which generated water accumulates in the MPL15 occurs easily, and gas diffusion and drainage properties decrease, resulting in a decrease in cell performance. That is, if there are many surface cracks in MPL15, the adhesion between the catalyst layer 13 and the gas diffusion layer 14 decreases when the MPL15 is incorporated into the fuel cell 1, and voids are generated between the layers, and liquid water accumulates there, resulting in a decrease in moisture management. On the other hand, it is possible to obtain a predetermined strength by increasing the thickness of the coating film, but if the thickness of MPL15 increases, the gas diffusion resistance increases, reducing gas diffusion properties and the like, leading to a decrease in cell performance. In contrast, the MPL coating pastes of Examples 1 to 7 provide a coating strength that is less susceptible to cracking of the MPL 15, and have good adhesion to the catalyst layer 13, thereby preventing flooding and enabling stable battery performance to be obtained without reducing gas and moisture permeability or moisture management.
[0120] Thus, in the MPL coating pastes of Examples 1 to 7, carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g is used, and the carbon black and fluororesin as a water-repellent resin are mixed in water in which a dispersant is dissolved, and they are stirred at high shear by a thin film swirling type high-speed stirrer, so that even carbon black with a highly developed structure can pass through a fine mesh filter with a mesh opening of 45 μm (300 mesh) that can remove foreign matter such as metals under a pressing force of 0.45 MPa without clogging. Therefore, it is possible to remove foreign matter such as metals in carbon black products that cause a decrease in durability and life of batteries without reducing productivity, and the durability of the battery can be improved.
[0121] Furthermore, in the case of carbon black with a DBP absorption within the range of 300 ml / 100 g to 500 ml / 100 g, even if the secondary aggregates are crushed to a few μm, the porosity of the structure is high, and when an MPL coating paste containing the carbon black is applied to a conductive porous substrate 16 and then dried and fired to form a cured coating film MPL 15, the high porosity due to the carbon black with high DBP absorption gives the cured coating film MPL 15 excellent gas and moisture permeability, and excellent gas diffusion and moisture management properties.
[0122] In particular, carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g can achieve both high porosity and crack resistance. That is, if the porosity of MPL 15 is too high, cracks are likely to occur in MPL 15, and if MPL 15 has cracks, durability is low and the properties of MPL 15 cannot be fully exhibited. Furthermore, moisture is likely to accumulate between the catalyst layer 13, which reduces moisture controllability and makes it difficult to obtain stable cell performance. In addition, water accumulated at the interface between the crack and catalyst layer 13 freezes below freezing point, causing MPL 15 and catalyst layer 13 to peel off and lose parts of them, which may adversely affect the performance of fuel cell 1 and shorten the life of fuel cell 1.
[0123] Carbon black with DBP absorption in the range of 300ml / 100g to 500ml / 100g has both high porosity and coating strength, and the good coating strength provides good adhesion to the catalyst layer 13, reduces unevenness in contact resistance, and allows for a uniform thickness, resulting in good electrical conductivity. In addition, cracks and flooding in the MPL 15, which causes water generated, are unlikely to occur. Furthermore, the gas diffusion layer 14 exhibits stable and excellent gas diffusion and moisture management properties, and stable high battery performance can be obtained because the carbon black can pass through a fine filter that can remove foreign matter such as metals without reducing productivity, as described above, and foreign matter such as metals can be removed there, resulting in good battery life and durability. Furthermore, carbon black with high DBP absorption can be expected to have an improved electrical conductivity due to a highly developed structure network.
[0124] According to the experimental research of the present inventors, the ratio of carbon black to water-repellent resin (solid content) is preferably within the range of 9 / 1 to 5 / 5 by weight. If the blending ratio of water-repellent resin (solid content) to carbon black is too low, the binding of carbon black by the resin content is weak, cracks are likely to occur in the cured coating film of MPL15, and the coating film strength is reduced. Furthermore, the binding property between MPL15 and the conductive porous substrate 16 is also reduced, and the contact resistance is increased. On the other hand, if the blending ratio of water-repellent resin (solid content) to carbon black is too high, the resin content becomes too high, and the resin content blocks the voids (gaps between carbon particles), resulting in a decrease in porosity and gas diffusibility. If the ratio of carbon black to water-repellent resin (solid content) is preferably within the range of 9 / 1 to 5 / 5 by weight, a cured coating film of a microporous layer that is less likely to crack, has high coating film strength, and has high gas diffusibility can be obtained.
[0125] Furthermore, according to the experimental research of the present inventors, the solid content ratio of the MPL coating paste is preferably 5% by mass or more and 40% by mass or less. If the solid content ratio of carbon, water-repellent resin, etc. is too small, the shrinkage stress during MPL film formation may increase, making the cured coating film of MPL15 more likely to crack and reducing the coating film strength. On the other hand, if the solid content ratio is too large, the porosity decreases and the gas diffusibility decreases. If the solid content ratio of the MPL coating paste is preferably 5% by mass or more and 40% by mass or less, a cured coating film of MPL15 that is less likely to crack, has high coating film strength, and has high gas diffusivity can be obtained. More preferably, it is 5% by mass or more and 30% by mass or less, and even more preferably, it is 5% by mass or more and 25% by mass or less.
[0126] According to the inventors' experimental research, the peripheral speed is preferably 25 m / s or more in the stirring by the thin film rotation method. If the peripheral speed is too slow, the secondary aggregates of carbon with a high DBP absorption amount are not sufficiently broken down, and when passing through a fine filter with a mesh size of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) for removing iron foreign matter that impairs the durability of the catalyst layer 13, that is, the durability and life of the battery, clogging occurs, productivity decreases, and it becomes difficult to pass through the filter, which reduces the durability and life of the battery. In addition, the coating property decreases, the cured coating film has a poor surface, and the adhesion with the catalyst layer 13 decreases, so that the generated water accumulates in the MPL 15, which makes it easy for flooding to occur and the drainage property decreases. On the other hand, as shown in Example 2, even if the peripheral speed is 50 m / s, the paste is unlikely to strike through the back when applied to the conductive porous substrate 16, and the gas diffusion property is also excellent. In particular, by increasing the peripheral speed, it is possible to reduce the secondary agglomerate diameter and to make the secondary agglomerate diameter uniform, thereby enabling the cured coating film to be made uniform.
[0127] Considering the performance limits of the high-speed agitator for the thin film swirling method, if the peripheral speed during stirring using the thin film swirling method is 25 m / s or more and 60 m / s or less, the secondary agglomerates of carbon with a high DBP absorption capacity will be sufficiently broken down to a secondary agglomerate size that can pass through a fine filter with a mesh opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), and good viscosity characteristics (flow characteristics) will be obtained, making it difficult for surface defects to occur during application and providing good coatability that ensures a sufficient coating width, resulting in good adhesion to the catalyst layer 13 and stable moisture management, resulting in stable battery performance, and also ensuring good battery durability and lifespan.
[0128] Furthermore, according to the inventors' experimental research, in the stirring at the above peripheral speed by the thin film swirling method, the stirring time is preferably 20 seconds or more, more preferably 25 seconds or more, and even more preferably 30 seconds or more. If the stirring time is too short, the secondary aggregates of carbon with a high DBP absorption amount are not sufficiently broken down, and when passing through a fine filter with a mesh size of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) for removing iron foreign matter that will impair the durability of the catalyst layer 13, i.e., the durability and life of the battery, clogging occurs, productivity decreases, and it becomes difficult to pass through the filter, thereby reducing the durability and life of the battery. On the other hand, if the stirring time is excessively long, the viscosity will be excessively reduced, causing the paste components to run through the back when applied to the conductive porous substrate 16. The viscosity can be increased by adding a thickener, but the use of the thickener will lengthen the firing time to decompose it, leading to high costs and reduced productivity due to the use of the thickener and the high load of firing. When the stirring time in the thin film swirling method is preferably 20 seconds or more and 200 seconds or less, more preferably 25 seconds or more and 150 seconds or less, and even more preferably 30 seconds or more and 100 seconds or less, secondary agglomerates of carbon with a high DBP absorption capacity are sufficiently disintegrated to a secondary agglomerate size that can pass through a fine filter with a mesh opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) without causing a decrease in productivity or an increase in cost, and good viscosity characteristics (flow characteristics) are obtained, making it difficult for surface defects to occur during application, and good coatability is obtained in which a sufficient coating width is ensured, resulting in good adhesion to the catalyst layer 13 and stable moisture management, resulting in stable battery performance, and also ensuring good battery durability and lifespan.
[0129] In addition, according to the inventors' experimental research, the shear rate of the MPL coating paste is 50 S -1The viscosity at is preferably 0.05 Pa·s or more and 1.0 Pa·s or less, more preferably 0.1 Pa·s or more and 0.9 Pa·s or less, and even more preferably 0.1 Pa·s or more and 0.5 Pa·s or less. If the viscosity is too low, the paste will penetrate through the conductive porous substrate 16 when applied to the conductive porous substrate 16, blocking the voids in the conductive porous substrate 16 and reducing the permeability to gas and moisture. On the other hand, if the viscosity is too high, the surface smoothness when applied to the conductive porous substrate 16 will decrease, and it will be difficult to apply the paste at the desired coating width, resulting in reduced productivity and poor coatability. Furthermore, when passing through a fine filter with a mesh opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) that can remove foreign matter such as metal components that will impair the durability of the catalyst layer 13, the pressure loss will increase and it will be difficult to pass through the filter. The shear rate of the MPL coating paste is 50 S -1 When the viscosity in is preferably 0.05 Pa·s or more and 1.0 Pa·s or less, more preferably 0.1 Pa·s or more and 0.9 Pa·s or less, and even more preferably 0.1 Pa·s or more and 0.9 Pa·s or less, good viscosity characteristics that enable passage through a fine filter with a mesh opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) can be obtained, good productivity can be obtained, good coatability can be obtained in which surface defects are unlikely to occur during coating and a sufficient coating width can be ensured, good adhesion to the catalyst layer 13 is achieved, stable moisture control can be ensured, and stable battery performance can be obtained, and furthermore, the durability and life of the battery can be well ensured.
[0130] As described above, the coating paste for forming a microporous layer in the above embodiment is a coating paste for forming a microporous layer containing carbon black, a water-repellent resin, a dispersant and a solvent, and the carbon black has a DBP absorption amount in the range of 300 ml / 100 g or more and 500 ml / 100 g or less and has a secondary aggregation diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less).
[0131] Therefore, according to the coating paste for forming the microporous layer of this embodiment, the secondary aggregates of carbon black with high DBP absorption are crushed, so that the viscosity increase of the paste is suppressed, and the MPL 15 can be formed with good coating properties on the surface of the conductive porous substrate 16. In the MPL 15, the carbon black with high DBP absorption has a high porosity due to its high structure, so that the porosity (air porosity) is high and the pores are uniformly distributed, and the highly structured structure forms gas and moisture passages, thereby improving the diffusibility and drainage of gas and moisture. In addition, the MPL 15 can be made to have good smoothness, so that good adhesion with the catalyst layer 13 can be obtained. Therefore, flooding is unlikely to occur, and the gas diffusibility and moisture management of the gas diffusion layer 14 can be improved, and the battery output, power generation performance can be stabilized, and the battery performance can be improved.
[0132] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregate diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the good coatability of the paste ensures good surface smoothness in MPL 15, and can achieve both high porosity and coating strength that is less susceptible to cracking. Therefore, by forming an MPL 15 that has high porosity but good surface smoothness, is less susceptible to cracking, and has good adhesion to catalyst layer 13, the MPL 15 is less likely to accumulate moisture, has high drainage, maintains high gas diffusivity, and also has good durability.
[0133] In addition, when carbon black having a DBP absorption amount within the range of 300 ml / 100 g to 500 ml / 100 g has a secondary agglomeration diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the carbon black is of a size that can pass through a fine mesh filter that enables the removal of foreign matter such as iron that affects the durability and lifespan of the catalyst layer 13 in which the cell reaction takes place, and is therefore unlikely to reduce the durability and lifespan of the battery. Therefore, it is possible to form an MPL 15 with high porosity, improve the gas and moisture permeability of the MPL 15, and improve the gas diffusivity and moisture management performance of the gas diffusion layer 14 in which the MPL 15 is formed.
[0134] Furthermore, in the coating paste for forming a microporous layer of the above embodiment, if the weight ratio of carbon black to water-repellent resin is within the range of 9 / 1 to 5 / 5, the resin components in the cured coating film of MPL15 formed will have good adhesion (binding properties) and will be less likely to crack, and clogging of voids due to excess resin will be suppressed. This makes it possible to achieve both the coating film strength of MPL15 and the permeability to gas and moisture, thereby enabling the gas diffusion layer 14 to exhibit high gas diffusivity and moisture controllability more effectively.
[0135] In addition, in the coating paste for forming the microporous layer of the above embodiment, the shear rate is 50 s -1 If the viscosity at 200° C. is within the range of 0.05 Pa·s to 1.0 Pa·s, then it is possible to suppress strike-through of the paste (the phenomenon in which the paste penetrates to the back surface of the conductive porous substrate opposite to the surface to which the paste is applied) when the paste is applied to the conductive porous substrate 16 constituting the gas diffusion layer 14, and it is possible to form a cured coating film of MPL 15 with good smoothness at a desired coating width, resulting in good coatability. Thus, a smooth MPL 15 can be obtained without reducing the porosity of the conductive porous substrate 16, and adhesion to the catalyst layer 13 can be improved, so that the gas diffusion properties and moisture management properties of the gas diffusion layer 14 are more stabilized.
[0136] Furthermore, the above embodiment can be regarded as an invention of a method for producing a coating paste for forming a microporous layer, which contains carbon black, a water-repellent resin, a dispersant, and a solvent, in which carbon black having a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and a water-repellent resin are mixed into a solvent containing a dispersant, and the mixture is stirred by a thin film swirling method.
[0137] According to the manufacturing method of the coating paste for forming a microporous layer of the above embodiment, the secondary agglomerates of carbon black with high DBP absorption can be broken down by dispersing the compounding material with a high shear by the thin film swirling method, and the increase in viscosity of the paste can be suppressed. Preferably, the secondary agglomerates of carbon black with high DBP absorption can be broken down with high efficiency by dispersing the compounding material with stirring at a peripheral speed of 25 m / s to 60 m / s.
[0138] Therefore, the coating paste for forming the microporous layer, in which the secondary aggregates of carbon black with high DBP absorption are broken down and the increase in viscosity is suppressed, can be applied to the surface of the conductive porous substrate 16 with good coating properties, and the MPL 15 formed by drying and baking the applied paste has a high porosity due to the high structure of the carbon black with high DBP absorption, and the porosity (air porosity) is high and the pores are uniformly distributed. Therefore, the highly structured structure allows the formation of gas and moisture passages, which can improve the diffusibility and drainage of gas and moisture. In addition, the MPL 15 can be made to have good smoothness, and therefore good adhesion with the catalyst layer 13 can be obtained. Therefore, flooding is unlikely to occur, and the gas diffusibility and moisture management of the gas diffusion layer 14 can be improved, and the battery output and power generation performance can be stabilized.
[0139] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the MPL15 has good surface smoothness due to the good coatability of the paste, and can achieve both high porosity and coating strength that is less likely to crack. Therefore, by forming an MPL15 that has high porosity but good surface smoothness, is less likely to crack, and has good adhesion to the catalyst layer 13, the MPL15 is less likely to accumulate moisture, has high drainage, maintains high gas diffusivity, and also has good durability. Therefore, the MPL coating paste can form the MPL 15 that has a high porosity and can improve the diffusivity and moisture management performance of the gas diffusion layer 14.
[0140] Furthermore, the above embodiment can also be regarded as an invention of a method for producing a coating paste for forming a microporous layer, which contains carbon black, a water-repellent resin, a dispersant, and a solvent, in which carbon black having a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and a water-repellent resin are mixed into a solvent containing a dispersant, and the mixture is stirred at a peripheral speed of 25 m / s or more and 60 m / s or less.
[0141] According to the manufacturing method of the coating paste for forming a microporous layer of the above embodiment, the secondary agglomerates of carbon black with high DBP absorption can be broken down by dispersing the compounding material with a high shear speed of 25 m / s or more and 60 m / s or less, and the increase in viscosity of the paste can be suppressed. Preferably, the secondary agglomerates of carbon black with high DBP absorption can be broken down with high efficiency by dispersing the compounding material with stirring at a peripheral speed of 25 m / s to 60 m / s.
[0142] Therefore, the coating paste for forming the microporous layer, in which the secondary aggregates of carbon black with high DBP absorption are broken down and the increase in viscosity is suppressed, can be applied to the surface of the conductive porous substrate 16 with good coating properties, and the MPL 15 formed by drying and baking the applied paste has a high porosity due to the high structure of the carbon black with high DBP absorption, and the porosity (air porosity) is high and the pores are uniformly distributed. Therefore, the highly structured structure allows the formation of gas and moisture passages, which can improve the diffusibility and drainage of gas and moisture. In addition, the MPL 15 can be made to have good smoothness, and therefore good adhesion with the catalyst layer 13 can be obtained. Therefore, flooding is unlikely to occur, and the gas diffusibility and moisture management of the gas diffusion layer 14 can be improved, and the battery output and power generation performance can be stabilized.
[0143] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the MPL15 has good surface smoothness due to the good coatability of the paste, and can achieve both high porosity and coating strength that is less likely to crack. Therefore, by forming an MPL15 that has high porosity but good surface smoothness, is less likely to crack, and has good adhesion to the catalyst layer 13, the MPL15 is less likely to accumulate moisture, has high drainage, maintains high gas diffusivity, and also has good durability. Therefore, the MPL coating paste can form the MPL 15 that has a high porosity and can improve the diffusivity and moisture management performance of the gas diffusion layer 14.
[0144] Furthermore, in the manufacturing method of the coating paste for forming the microporous layer of the above embodiment, when a mixture of a dispersant, a solvent, carbon black, and a water-repellent resin is pre-mixed with a mixer such as Disper or a turbine-stator type mixer at a peripheral speed of 1 m / s to 20 m / s before stirring by the thin film swirling method or the like or at a peripheral speed of 25 m / s to 60 m / s, that is, when the mixture is dispersed by a low shear at a peripheral speed of 1 m / s to 20 m / s with a mixer such as Disper or a turbine-stator type mixer, and then dispersed by a high shear at a peripheral speed of 25 m / s to 60 m / s by the thin film swirling method or the like, it is possible to suppress the variation in the distribution of the secondary agglomeration diameter of the carbon black, and it is possible to form a homogeneous MPL15 by suppressing the variation in the distribution of voids, and to obtain stable gas and moisture permeability. Therefore, it becomes an MPL coating paste that can form an MPL15 that can suppress the variation in the distribution of voids and obtain stable performance. In particular, if a mixer such as a Disper or turbine-stator type mixer is used for pre-mixing, a paste with fewer air bubbles can be obtained by mixing and degassing.
[0145] In addition, according to the manufacturing method of the coating paste for forming a microporous layer of the above embodiment, the mixture is passed through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less) after stirring at a peripheral speed of 25 m / s to 60 m / s by a thin film spinning method or the like, so that the catalyst layer 13 contains less foreign matter such as iron that affects the durability and lifespan of the catalyst layer 13. Therefore, the durability of the fuel cell 1 can be well maintained. In other words, the MPL coating paste can form an MPL 15 that does not reduce the durability and lifespan of the fuel cell 1.
[0146] In the above-mentioned method for producing a coating paste for forming a microporous layer, if the weight ratio of carbon black to water-repellent resin is within the range of 9 / 1 to 5 / 5, the adhesiveness (binding property) of the resin in the cured coating film of MPL15 formed is good, cracks are unlikely to occur, and clogging of voids due to excess resin is suppressed. Therefore, the MPL coating paste can form MPL15 that can achieve both coating film strength and gas and moisture permeability.
[0147] In addition, in the method for producing the coating paste for forming the microporous layer, -1 If the viscosity at 200° C. is within the range of 0.05 Pa·s to 1.0 Pa·s, then it is possible to suppress strike-through of the paste when it is applied to the conductive porous substrate 16 that constitutes the gas diffusion layer 14, and it is possible to form a cured coating film of MPL 15 with good smoothness at the desired coating width, resulting in good coatability. Thus, a smooth MPL 15 can be obtained without reducing the porosity of the conductive porous substrate 16, and adhesion to the catalyst layer 13 can be improved, resulting in an MPL coating paste that can form an MPL 15 that ensures stable performance.
[0148] Furthermore, the above embodiment can also be considered as an invention of a gas diffusion layer 14 for a fuel cell that is composed of a conductive porous substrate 16 made of conductive fibers or the like, and an MPL 15 made of carbon black and a water-repellent resin formed on the surface of the conductive porous substrate 16, in which the carbon black in the MPL 15 has a secondary aggregation diameter that allows carbon black with a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g to pass through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less).
[0149] According to the gas diffusion layer 14 for fuel cells of the present embodiment, the carbon black of the MPL 15 made of the water-repellent resin and the carbon black formed on the surface of the conductive porous substrate 16 made of conductive fibers or the like has a secondary aggregate diameter that passes through a mesh (100 mesh or more, 400 mesh or less) with an opening of 34 μm or more and 154 μm or less, and the secondary aggregates of the carbon black with high DBP absorption are crushed, so that the viscosity increase of the paste forming the MPL 15 is suppressed, and in the MPL 15 formed with good coating properties on the surface of the conductive porous substrate 16, the carbon black with high DBP absorption has a high porosity due to the high structure, and the porosity (air porosity) is high and the pores are uniformly distributed. Therefore, the diffusion and drainage of gas and moisture can be improved by forming a gas and moisture passage due to the high structure structure. Furthermore, by providing the MPL 15 with good smoothness, good adhesion to the catalyst layer 13 can be obtained. Therefore, flooding is unlikely to occur, and the gas diffusion and moisture management properties of the gas diffusion layer 14 can be improved, leading to stabilization of the battery output and power generation performance.
[0150] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), MPL15 has good surface smoothness due to the good coatability of the paste, and can achieve both high porosity and coating strength that is less likely to crack. Therefore, MPL15, which has high porosity but good surface smoothness, is less likely to crack, and has good adhesion to catalyst layer 13, is less likely to accumulate moisture, has high drainage, maintains high gas diffusivity, and also has good durability.
[0151] In addition, when carbon black having a DBP absorption amount within the range of 300 ml / 100 g to 500 ml / 100 g has a secondary agglomeration diameter that passes through a mesh with an opening of 34 μm or more and 154 μm or less (100 mesh or more and 400 mesh or less), the carbon black is of a size that can pass through a fine mesh filter that enables the removal of foreign matter such as iron that affects the durability and lifespan of the catalyst layer 13 in which the cell reaction takes place, and is therefore unlikely to reduce the durability and lifespan of the battery 1. Therefore, according to the gas diffusion layer 14 for the fuel cell of the above embodiment, since it has the MPL 15 with a high porosity, it is possible to improve the permeability of gas and moisture, and it is possible to improve the performance of gas diffusion and moisture management.
[0152] Furthermore, in the gas diffusion layer 14 for the fuel cell of the above embodiment, if the weight ratio of carbon black and water-repellent resin in the MPL 15 is within the range of 9 / 1 to 5 / 5, the adhesiveness (binding) due to the resin content in the cured coating film of the MPL 15 is good, cracks are less likely to occur, and clogging of voids due to excess resin content is suppressed, so that the gas diffusion layer 14 exhibits good moisture and gas permeability.
[0153] In the gas diffusion layer for a fuel cell in the above embodiment, the carbon black in the microporous layer formed on the surface of the conductive porous substrate and made of carbon black and water-repellent resin has a secondary aggregate diameter that allows carbon black with a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g to pass through a mesh with an opening size in the range of 34 to 154 μm.
[0154] The conductive porous substrate is a gas diffusion layer electrode substrate, which is conductive and has a porous body with an average pore size larger than that of the microporous layer. For example, a porous substrate made of carbon fiber (e.g., graphite fiber, etc.) such as carbon fiber woven fabric, carbon fiber paper, carbon fiber nonwoven fabric, carbon felt, carbon paper, and carbon cloth, and a metal porous substrate such as foamed sintered metal, metal mesh, and expanded metal are used. The microporous layer is formed by applying a coating paste for forming a microporous layer, containing carbon black and a water-repellent resin, to the surface of the conductive porous substrate, followed by drying and baking, in which the carbon black is bound with the water-repellent resin. The carbon black has a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and has a secondary agglomeration diameter that allows the carbon black to pass through a mesh with an opening size in the range of 34 to 154 μm.
[0155] Examples of the carbon black that can be used herein include furnace black, thermal black, ketjen black, and acetylene black. Acetylene black is preferred because it is capable of forming a microporous layer that has high gas diffusivity, strength, electrical conductivity, and the like. The carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g and a secondary aggregate size that passes through a mesh with an opening of 34 to 154μm means that the secondary aggregates (several tens of μm) of the carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g are disintegrated (disaggregated) by high shear dispersion to a secondary aggregate size (several μm) that can pass through a mesh with an opening of 34μm to 154μm, i.e., 100 mesh to 400 mesh. In other words, the carbon black having a DBP absorption in the range of 300ml / 100g to 500ml / 100g is disintegrated to have a secondary aggregate size that can pass through a mesh with an opening of 34 to 154μm (100 to 400 mesh).
[0156] According to the above embodiment of the gas diffusion layer for a fuel cell, the carbon black in the microporous layer made of carbon black and water-repellent resin formed on the surface of a conductive porous substrate made of conductive fibers or the like has a secondary agglomerate diameter that passes through a mesh with an opening of 34 μm or more and 150 μm or less, and the carbon black has a DBP absorption within the range of 300 ml / 100 g to 500 ml / 100 g, and the secondary agglomerates of carbon black with high DBP absorption are crushed. Therefore, an increase in viscosity of the paste forming the microporous layer is suppressed, and the microporous layer is formed with good coatability on the surface of the conductive porous substrate, and the carbon black with high DBP absorption has a high porosity due to its high structure, resulting in a high porosity (air porosity).
[0157] In particular, when carbon black with DBP absorption in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary aggregation diameter that passes through a mesh with an opening of 34 to 154 μm, the microporous layer has good surface smoothness due to the good coatability of the paste, and high porosity and coating strength that is less likely to cause cracks can be achieved at the same time. Therefore, a microporous layer with high porosity, good surface smoothness, few cracks, and good adhesion to the catalyst layer is less likely to accumulate moisture, has high drainage, maintains high gas diffusivity, and has good durability. In addition, carbon black with a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g has a secondary agglomeration diameter that passes through a mesh with an opening size of 34 μm or more and 150 μm or less, and is of a size that can pass through a fine mesh filter that enables the removal of foreign matter such as iron that affects the durability and lifespan of the catalyst layer in which the cell reaction takes place, and is therefore unlikely to reduce the durability and lifespan of the battery. Thus, the gas diffusion layer for a fuel cell according to the above embodiment has a microporous layer with a high porosity, so that the gas diffusion layer can have improved gas diffusivity and moisture management performance.
[0158] The carbon black and the water-repellent resin in the microporous layer of the gas diffusion layer for the fuel cell in the above embodiment have a solid weight ratio of 9 / 1≦carbon black / water-repellent resin≦5 / 5.
[0159] According to the gas diffusion layer for fuel cells of the above embodiment, the weight ratio of carbon black to water-repellent resin is within the range of 9 / 1 to 5 / 5, so that the adhesion (binding, binder effect) of the resin in the cured coating of the microporous layer is good, cracks are less likely to occur, and clogging of voids due to excess resin is suppressed. Therefore, the microporous layer can achieve both coating strength and gas and moisture permeability.
[0160] The MPL coating paste of this embodiment and the fuel cell gas diffusion layer 14 produced using it are not limited to the solid polymer fuel cell 1, but can also be applied to other fuel cells, such as direct methanol fuel cells. In addition, when implementing the present invention, the composition, ingredients, blending amounts, materials, and other manufacturing processes of the MPL coating paste and other parts of the fuel cell gas diffusion layer 14 are not limited to those in this embodiment. Furthermore, the above-mentioned numerical ranges are not strict, and are of course approximate values including errors due to measurements, etc., and errors of several tens of percent are not denied. Furthermore, the numerical values given in the embodiments of the present invention do not indicate critical values, but indicate appropriate values suitable for implementation, so even if the numerical values are slightly changed, the implementation is not denied. [Explanation of symbols]
[0161] 1 fuel cell 14 Gas diffusion layer 15 Microporous layer 16 Conductive porous substrate
Claims
1. A coating paste for forming a microporous layer, comprising carbon black, a water-repellent resin, a dispersant, and a solvent, The carbon black has a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and has a secondary agglomeration size that allows the carbon black to pass through a mesh with an opening size in the range of 34 to 154 μm, The coating paste for forming a microporous layer is characterized in that the viscosity at a shear rate of 50 s -1 is within the range of 0.05 Pa·s to 1.0 Pa·s.
2. The coating paste for forming a microporous layer according to claim 1, characterized in that the weight ratio of the carbon black to the water-repellent resin is within the range of 9 / 1 to 5 / 5.
3. A method for producing a coating paste for forming a microporous layer, comprising: A method for producing a coating paste for forming a microporous layer, comprising mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and a water-repellent resin in a solvent containing a dispersant, and stirring the mixture by a thin film swirling method.
4. A method for producing a coating paste for forming a microporous layer, comprising: A method for producing a coating paste for forming a microporous layer, comprising mixing carbon black having a DBP absorption amount in the range of 300 ml / 100 g to 500 ml / 100 g and a water-repellent resin with a solvent containing a dispersant, and stirring the mixture at a peripheral speed of 25 m / s or more and 60 m / s or less.
5. The method for producing a coating paste for forming a microporous layer according to claim 3 or 4, characterized in that after the stirring, the mixture is passed through a mesh having an opening of 34 to 154 μm.
6. The method for producing a coating paste for forming a microporous layer according to claim 3 or 4, characterized in that pre-stirring is performed with a disperser or turbine stator type stirrer before the stirring.
7. The method for producing a coating paste for forming a microporous layer according to claim 3 or 4, characterized in that, before the stirring, pre-stirring is performed at a peripheral speed of 1 m / s or more and 20 m / s or less.
8. The method for producing a coating paste for forming a microporous layer according to claim 3 or 4, characterized in that the weight ratio of the carbon black to the water-repellent resin is within the range of 9 / 1 to 5 / 5.
9. The coating paste for forming the microporous layer is applied at a shear rate of 50 s -1 The method for producing a coating paste for forming a microporous layer according to claim 3 or 4, characterized in that the viscosity at 0.05 Pa·s to 1.0 Pa·s is within the range.
Citation Information
Patent Citations
Gas diffusion layer, preparation method and application thereof
CN114094124A
Method of manufacturing electrode for fuel cell
JP2003100305A
Manufacturing method of electrode for fuel cell, electrode for fuel cell, coating composition, manufacturing method for, the composition solid polymer fuel cell, manufacturing method for the cell
JP2003123774A
Pre-compressed gas diffusion layer for electrochemical cells
JP2005520311A
Moisture control sheet, gas diffusion sheet, membrane-electrode assembly, and solid polymer fuel cell
JP2010192361A